Polyamide composition and molded article
By adding a specific proportion of phosphorus-containing flame retardant and an inorganic filler material to the polyamide composition, the shortcomings of the polyamide composition in the prior art in terms of low-temperature impactability, load flexural temperature and flame retardancy are solved, and a high-performance polyamide composition is achieved.
Patent Information
- Application Number
- CN202411489368.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-27
- Filing Date
- 2024-10-24
- Publication Date
- 2025-04-29
AI Technical Summary
There is room for improvement in the existing polyamide compositions in terms of low-temperature impactability, load flexural temperature and V-0 flame retardancy in UL94V tests.
A combination of 20-60% by weight of polyamide, 10-30% by weight of phosphorus flame retardant, 2-20% by weight of polyamide elastomer and 10-60% by weight of inorganic filler material is used, and the phosphorus flame retardant includes phosphinates, diphosphinates and their condensates.
It has achieved a polyamide composition with excellent low-temperature impact, high heat resistance, excellent electrical characteristics and excellent flame retardancy, and is suitable for high-performance molded products.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a polyamide composition and a molded article. Background Art
[0002] Polyamides such as polyamide 66 (hereinafter also referred to as "PA66") have excellent molding processability, mechanical properties, and chemical resistance, and are therefore widely used as various component materials for automobiles, electrical and electronic applications, industrial materials, industrial materials, and daily and household products.
[0003] Polyamides are often flame-retarded by adding halogen compounds. However, recently, various regulations have been made to prevent the use of products containing halogen compounds in electrical and electronic parts, based on hazardous substance regulations such as RoHS (Restriction of Hazardous Substances) and PoHS (Prohibition on Certain Hazardous Substances in Consumer Products). Therefore, various halogen-free flame retardants for polyamides have been developed.
[0004] Examples of the halogen-free flame retardant include phosphorus compounds. The use of calcium salts and aluminum salts of phosphinic acid or diphosphinic acid as flame retardants for polyamides is disclosed.
[0005] Recently, solar power generation has attracted attention again from the perspective of sustainability. Solar power generation modules are mostly installed outdoors, and thermoplastic resins used to form connection structures such as junction boxes and connectors are required to have electrical insulation properties represented by tracking resistance, excellent flame retardancy, mechanical properties, impact properties, water resistance, chemical resistance, and dimensional stability, in addition to the performance required for electrical and electronic components in the past, as well as impact strength at low temperatures.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-43762
[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-50323
[0010] Patent Document 3: International Publication No. 2021 / 257531 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, the technology disclosed in Patent Document 1 discloses a non-reinforced polyamide composition using polyamide 12, polyamide 12 elastomer, and phosphinate metal salt in order to improve impact resistance, but there is room for improvement in low-temperature impact resistance and load deflection. The technology disclosed in Patent Document 2 discloses a reinforced polyamide composition using polyamide 66 and polyamide 6I, but there is room for improvement in impact resistance. Patent Document 3 discloses a non-reinforced polyamide using a polyamide elastomer and phosphinate metal salt, but there is room for improvement in heat resistance.
[0013] It can be seen that in the prior art, the actual situation is that there is no known polyamide composition that can achieve low-temperature impact resistance, load deflection temperature, and V-0 in the UL94V test.
[0014] The present invention has been made in view of the above circumstances, and provides a polyamide composition having excellent low-temperature impact resistance, high heat resistance, excellent electrical properties, and excellent flame retardancy, and a molded article using the polyamide composition.
[0015] Means used to solve problems
[0016] That is, the present invention includes the following aspects.
[0017] [1] A polyamide composition, comprising: 20% to 60% by weight of (A) a polyamide, 10% to 30% by weight of (B) a phosphorus-containing flame retardant, 2% to 20% by weight of (C) a polyamide elastomer, and 10% to 60% by weight of (D) an inorganic filler.
[0018] [2] The polyamide composition according to [1], wherein the (B) phosphorus-containing flame retardant comprises at least one phosphinate selected from the group consisting of a phosphinate represented by the following general formula (1), a diphosphinate represented by the following general formula (2) and their condensates, and a complex salt of a phosphinate and a phosphonate represented by the following general formula (3).
[0019]
[0020] In the general formula (1), R 11 and R 12 Each independently represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. n11+ is a metal ion with a valence of n11. M is an element belonging to Group 2 or Group 15 of the Periodic Table, a transition element, zinc or aluminum. n11 is 2 or 3. In the case where n11 is 2 or 3, the presence of multiple R 11 and multiple R 12 Each may be the same or different.
[0021] In general formula (2), R 21 and R 22 Each is independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. 21 M' is an alkylene group having 1 to 10 carbon atoms or an arylene group having 6 to 10 carbon atoms. x m21+ is a metal ion with a valence of m21. M' is an element belonging to Group 2 or Group 15 of the Periodic Table, a transition element, zinc or aluminum. n21 is an integer greater than 1 and less than 3. When n21 is 2 or 3, the presence of multiple R 21 , multiple R 22 and multiple Y 21 Each may be the same or different. m21 is 2 or 3. x is 1 or 2. When x is 2, the multiple M's present may be the same or different. n21, x and m21 are integers satisfying the relationship of 2×n21=m21×x.
[0022] In the general formula (3), R1, R2 and R3 are each independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. m+ It is a metal ion with a valence of m. M is an element belonging to Group 2 or Group 15 of the periodic table, a transition element, zinc or aluminum. m is 2 or 3. When m is 2 or 3, the multiple R1s, multiple R2s and multiple R3s present may be the same or different. a and b are both 0.01 or more and 10 or less, satisfying m=a+2b.
[0023] [3] The polyamide composition according to [1] or [2], wherein the (B) phosphorus-containing flame retardant comprises a phosphinic acid metal salt or a phosphinic acid-phosphonic acid composite metal salt.
[0024] [4] The polyamide composition according to [1] or [2], wherein the (C) polyamide elastomer is a polyamide elastomer based on polyamide 6.
[0025] [5] The polyamide composition according to [1] or [2], wherein the (A) polyamide is (A-1) a crystalline polyamide.
[0026] [6] The polyamide composition according to [1] or [2], wherein the (A) polyamide further comprises (A-2) amorphous polyamide.
[0027] [7] The polyamide composition according to [6], wherein the (A-2) amorphous polyamide contains 50 mol % or more of isophthalic acid units in all dicarboxylic acid units.
[0028] [8] The polyamide composition according to [6], wherein the total dicarboxylic acid units constituting the (A-2) amorphous polyamide contain 75 mol % or more of isophthalic acid units.
[0029] [9] The polyamide composition according to [6], wherein the total dicarboxylic acid units constituting the (A-2) amorphous polyamide contain 100 mol % of isophthalic acid units.
[0030] Effects of the Invention
[0031] According to the polyamide composition of the above aspect, it is possible to provide a polyamide composition having high low-temperature impact resistance, excellent deflection under load, and excellent flame retardancy when formed into a molded article. DETAILED DESCRIPTION
[0032] Hereinafter, a method for implementing the present invention (hereinafter referred to as "this embodiment") is described in detail. The following this embodiment is an example for explaining the present invention and is not intended to limit the present invention to the following content. The present invention can be implemented by appropriately modifying it within the scope of its purpose.
[0033] In addition, in this specification, "polyamide" refers to a polymer having an amide (-NHCO-) group in the main chain.
[0034] <Polyamide composition>
[0035] The polyamide composition of the present embodiment includes: 20 wt % to 60 wt % of (A) polyamide, 10 wt % to 30 wt % of (B) phosphorus-containing flame retardant, 2 wt % to 20 wt % of (C) polyamide elastomer, and 10 wt % to 60 wt % of (D) inorganic filler.
[0036] <(A) Polyamide>
[0037] Examples of the polyamide (A) include polycaprolactam (polyamide 6), polybutylene adipamide (polyamide 46), polyhexamethylene adipamide (polyamide 66), polyhexamethylene cyclohexane dicarboxamide (polyamide 6C), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecane dicarboxamide (polyamide 612), polyundecalactam (polyamide 11), polydodecalactam (polyamide 12), polyhexamethylene isophthalamide (polyamide 6I), polyhexamethylene terephthalamide (polyamide 6T), polynonamethylene terephthalamide (polyamide 9T), polydodecane terephthalamide (polyamide 12T), polymethylene adipamide (polyamide MXD6), and polyamide copolymers obtained by copolymerizing two or more of these polyamides. These polyamides may be used alone or in combination of two or more.
[0038] The (A-1) crystalline polyamide has a melting point (Tm) of 290.0°C or lower, preferably 280.0°C or lower, more preferably 220.0°C to 280.0°C, further preferably 220.0°C to 270.0°C, particularly preferably 240.0°C to 270.0°C.
[0039] When the melting point Tm of the crystalline polyamide (A-1) is within the above range, the polyamide composition can be excellent in melt processing such as extrusion and molding, can further suppress thermal decomposition of the phosphorus-containing flame retardant, and has an excellent deflection temperature under load.
[0040] (A-1) The melting point Tm of the crystalline polyamide can be measured in accordance with JIS-K7121. Examples of the measuring apparatus include a differential scanning calorimeter (DSC), and more specifically, Diamond-DSC manufactured by PERKIN-ELMER.
[0041] The content of the amorphous polyamide (A-2) is 10.0% by mass or more and 50.0% by mass or less, preferably 10.0% by mass or more and 45.0% by mass or less, more preferably 12.5% by mass or more and 45.0% by mass or less, further preferably 15.0% by mass or more and 42.5% by mass or less, further preferably 17.5% by mass or more and 40.0% by mass or less, and particularly preferably 20.0% by mass or more and 35.0% by mass or less. When the content of the amorphous polyamide (A-2) is within the above range, a polyamide composition having excellent moldability such as rigidity under atmospheric equilibrium moisture absorption, flame retardancy, and plasticization stability can be obtained. In addition, the polyamide composition containing a component represented by an inorganic filler has excellent load deflection.
[0042] The polyamide composition of the present embodiment has the above-mentioned structure and can provide a polyamide composition which is excellent in melt processing such as extrusion and molding, can further suppress thermal decomposition of the phosphorus-containing flame retardant, has excellent deflection temperature under load, good moldability, and excellent flame retardancy.
[0043] In addition, below, (A) polyamide, (B) phosphorus-containing flame retardant, (C) polyamide elastomer and (D) inorganic filler may be respectively referred to as (A) component, (B) component, (C) component and (D) component.
[0044] 《Characteristics of polyamide compositions》
[0045] The melting point Tm of the polyamide composition of the present embodiment can be the following configuration.
[0046] [Melting point Tm of polyamide composition]
[0047] The melting point Tm of the polyamide composition is preferably 330.0°C or less, more preferably 300.0°C or less, further more preferably 290.0°C or less, further preferably 280.0°C or less, further preferably 220.0°C to 280.0°C, particularly preferably 220.0°C to 270.0°C, and most preferably 240.0°C to 270.0°C.
[0048] By having the melting point Tm of the polyamide composition within the above range, a polyamide composition having excellent mechanical properties, particularly rigidity under atmospheric equilibrium moisture absorption, flame retardancy, and moldability can be obtained. In addition, a polyamide composition containing a component represented by an inorganic filler has excellent heat resistance represented by deflection temperature under load. On the other hand, by having the melting point Tm of the polyamide composition within the above range, a polyamide composition having more excellent thermal rigidity and the like can be obtained.
[0049] The melting point Tm of the polyamide composition can be measured in accordance with JIS-K7121. Examples of the measuring apparatus include Diamond-DSC manufactured by PERKIN-ELMER.
[0050] 《(A-1)Crystalline polyamide》
[0051] The crystalline polyamide refers to a polyamide having a crystal melting heat of 15 J / g or more when measured at 20° C. / min by a differential scanning calorimeter.
[0052] Examples of the crystalline polyamide (A-1) include, but are not limited to: (A-1a) polyamides obtained by ring-opening polymerization of lactams, (A-1b) polyamides obtained by self-condensation of ω-aminocarboxylic acids, (A-1c) polyamides obtained by condensation of diamines and dicarboxylic acids, and copolymers thereof. The crystalline polyamide may be used alone or in the form of a mixture of two or more.
[0053] Among them, as the crystalline polyamide, aliphatic amides whose carbon skeleton constituting a monomer unit contains an aliphatic hydrocarbon group are preferred.
[0054] Examples of the lactam used in the polyamide obtained by ring-opening polymerization of lactam (A-1a) include pyrrolidone, caprolactam, undecanolactam, and lauryl lactam, but are not limited thereto.
[0055] Examples of the ω-aminocarboxylic acid used in the polyamide obtained by self-condensation of ω-aminocarboxylic acid (A-1b) include, but are not limited to, ω-amino fatty acids which are ring-opening compounds of the lactams generated by water. Two or more monomers may be used in combination for condensation of the lactams or ω-aminocarboxylic acids.
[0056] Examples of the diamine (monomer) used in the polyamide obtained by condensing a diamine and a dicarboxylic acid (A-1c) include, but are not limited to, linear saturated aliphatic diamines having 2 to 20 carbon atoms, such as ethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, and tridecamethylenediamine.
[0057] Examples of the diamine constituting the diamine unit having a substituent branching from the main chain include, but are not limited to, branched saturated aliphatic diamines having 3 to 20 carbon atoms, such as 2-methylpentamethylenediamine (also called 2-methyl-1,5-diaminopentane), 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 2-methyl-1,8-octanediamine (also called 2-methyloctamethylenediamine), and 2,4-dimethyloctamethylenediamine.
[0058] Among them, as the diamine constituting the diamine unit having a substituent branching from the main chain, 2-methylpentamethylenediamine or 2-methyl-1,8-octanediamine is preferred, and 2-methylpentamethylenediamine is more preferred. The inclusion of such an aliphatic diamine tends to provide a polyamide composition having better heat resistance and rigidity.
[0059] The above-mentioned diamines as monomers may be used alone or in combination of two or more.
[0060] The number of carbon atoms in the diamine unit is preferably 4 or more and 12 or less, and more preferably 4 or more and 10 or less. When the number of carbon atoms in the diamine unit is equal to or greater than the above lower limit, heat resistance is more excellent, while when the number of carbon atoms in the diamine unit is equal to or less than the above upper limit, crystallinity and releasability are more excellent.
[0061] It should be noted that the aliphatic diamine may further contain a trivalent or higher-valent aliphatic amine such as bis-hexamethylenetriamine as necessary.
[0062] These diamines may be used alone or in combination of two or more.
[0063] Examples of the dicarboxylic acid (monomer) used in the polyamide obtained by condensing a diamine and a dicarboxylic acid (A-1c) include, but are not limited to: aliphatic dicarboxylic acids such as succinic acid, adipic acid, pimelic acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid; aromatic dicarboxylic acids such as isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, and 5-sodium sulfoisophthalic acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid, etc. The dicarboxylic acids as monomers may be used alone or in combination of two or more.
[0064] The crystalline polyamide (A-1) may further contain units derived from trivalent or higher polycarboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid, as necessary. The trivalent or higher polycarboxylic acids may be used alone or in combination of two or more.
[0065] Specific examples of the (A-1) crystalline polyamide include polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecanamide), polyamide 12 (polydodecamide), polyamide 46 (polybutylene adipamide), polyamide 56 (polypentamethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sebacamide), polyamide 612 (polyhexamethylene dodecaneamide), polyamide 4T (polybutylene terephthalamide), polyamide 6T (polyhexamethylene terephthalamide), polyamide 9T (polynonane terephthalamide), and copolymer polyamides containing these as constituent components.
[0066] Among them, polyamide 6, polyamide 46, polyamide 66 or polyamide 610 is preferred, polyamide 6, polyamide 66 or polyamide 610 is more preferred, polyamide 6 or polyamide 66 is further preferred, and polyamide 66 is particularly preferred. Polyamide 66 is excellent in heat resistance, moldability and toughness, and is therefore considered to be a suitable material for connector parts.
[0067] [(A-1) Characteristics of crystalline polyamide]
[0068] ((A-1) Weight average molecular weight Mw of crystalline polyamide)
[0069] As an indicator of the molecular weight of the (A-1) crystalline polyamide, the weight average molecular weight can be used.
[0070] The weight average molecular weight (Mw) of the (A-1) crystalline polyamide is preferably 10,000 to 50,000, more preferably 15,000 to 45,000, further preferably 20,000 to 40,000, particularly preferably 25,000 to 40,000.
[0071] When Mw is within the above range, a polyamide composition can be obtained that satisfies mechanical properties, particularly water absorption rigidity, thermal rigidity, fluidity, corrosion resistance, etc. In addition, a molded article obtained from a polyamide composition containing components represented by an inorganic filler has a more excellent surface appearance.
[0072] (A-1) The weight average molecular weight (Mw) of the crystalline polyamide can be measured using gel permeation chromatography (GPC).
[0073] ((A-1) Molecular weight distribution of crystalline polyamide)
[0074] The molecular weight distribution of the (A-1) crystalline polyamide is determined by dividing the weight average molecular weight (Mw) of the (A-1) crystalline polyamide by the number average molecular weight (Mn) of the (A-1) crystalline polyamide, i.e., Mw / Mn, as an index.
[0075] Mw / Mn is preferably 1.0 or more, more preferably 1.8 or more and 2.2 or less, and further preferably 2.0 or more and 2.2 or less.
[0076] When Mw / Mn is within the above range, a polyamide composition having better fluidity etc. can be obtained. In addition, a molded article obtained from a polyamide composition containing components represented by an inorganic filler has better surface appearance.
[0077] Examples of a method for controlling Mw / Mn within the above range include the method described in 1) or 2) below.
[0078] 1) A method of adding a known polycondensation catalyst such as phosphoric acid or sodium hypophosphite as an additive during hot melt polymerization of polyamide.
[0079] 2) In addition to the method 1) above, a method in which polymerization conditions such as heating conditions and reduced pressure conditions are controlled.
[0080] In addition, Mw / Mn can be calculated using Mw and Mn obtained by GPC.
[0081] [(A-1) Content of Crystalline Polyamide]
[0082] In the polyamide composition of the present embodiment, the content of the (A-1) crystalline polyamide can be set to 50.0 mass % or more and 90.0 mass % or less, preferably 55.0 mass % or more and 90.0 mass % or less, more preferably 55.0 mass % or more and 87.5 mass % or less, further preferably 57.5 mass % or more and 87.5 mass % or less, further preferably 60.0 mass % or more and 82.5 mass % or less, and particularly preferably 62.5 mass % or more and 80.0 mass % or less, relative to the total amount of polyamide in the polyamide composition.
[0083] By setting the blending amount of the (A-1) crystalline polyamide within the above range, a polyamide composition having more excellent mechanical properties, particularly thermal rigidity, fluidity, corrosion resistance, etc. can be obtained.
[0084] In the polyamide composition of the present embodiment, the content of the (A-1) crystalline polyamide can be, for example, 10.0 mass % to 60.0 mass % inclusive, 15.0 mass % to 55.0 mass % inclusive, 20.0 mass % to 53.0 mass % inclusive, or 25.0 mass % to 50.0 mass % inclusive, relative to the total mass of the polyamide composition.
[0085] 《(A-2)Amorphous polyamide》
[0086] Amorphous polyamide refers to a polyamide having a crystallization enthalpy ΔH of less than 15 J / g when measured at 20°C / min by a differential scanning calorimeter. The crystallization enthalpy of (A-2) the amorphous polyamide is preferably 10 J / g or less, more preferably 5 J / g or less, and further preferably 0 J / g. It should be noted that the crystallization enthalpy ΔH can be measured, for example, according to JIS-K7121 using a measuring device such as Diamond-DSC manufactured by PERKIN-ELMER.
[0087] The (A-2) amorphous polyamide is not particularly limited as long as it is a polyamide having a crystallization enthalpy ΔH of not more than the above upper limit, and may be a semi-aromatic polyamide.
[0088] When the (A-2) non-crystalline polyamide is a semi-aromatic polyamide, it is preferably a polyamide containing a diamine unit and a dicarboxylic acid unit.
[0089] The (A-2) amorphous polyamide is preferably a polyamide containing (A-2a) a dicarboxylic acid unit containing at least 50 mol % of an isophthalic acid unit and (A-2b) a diamine unit containing at least 50 mol % of a diamine unit having 4 to 10 carbon atoms.
[0090] The total amount of the isophthalic acid units and the diamine units having 4 to 10 carbon atoms is preferably 75 mol % to 100 mol %, more preferably 90 mol % to 100 mol %, and even more preferably 100 mol %, based on the total amount of all structural units of the amorphous polyamide (A-2).
[0091] In addition, in the present invention, the ratio of the predetermined monomer units constituting the (A-2) amorphous polyamide can be measured by nuclear magnetic resonance spectroscopy (NMR) or the like.
[0092] [(A-2a) dicarboxylic acid unit]
[0093] In the dicarboxylic acid units (A-2a), the content of the isophthalic acid units is preferably 50 mol % or more, particularly preferably 75 mol % or more and 100 mol % or less, further preferably 90 mol % or more and 100 mol % or less, particularly preferably 100 mol % based on the total molar amount of the dicarboxylic acid units.
[0094] When the content of the isophthalic acid unit relative to the total molar number of the dicarboxylic acid is at least the above lower limit, a polyamide composition having excellent mechanical properties, rigidity during atmospheric equilibrium moisture absorption, moldability, surface appearance, and flame retardancy can be obtained.
[0095] The (A-2a) dicarboxylic acid unit may contain an aromatic dicarboxylic acid unit, an aliphatic dicarboxylic acid unit, or an alicyclic dicarboxylic acid unit other than the isophthalic acid unit.
[0096] (Aromatic dicarboxylic acid unit)
[0097] Examples of the aromatic dicarboxylic acid constituting the aromatic dicarboxylic acid unit other than the isophthalic acid unit include, but are not limited to, dicarboxylic acids having a phenyl group or a naphthyl group. The aromatic group of the aromatic dicarboxylic acid may be unsubstituted or may have a substituent.
[0098] The substituent is not particularly limited, and examples thereof include an alkyl group having 1 to 4 carbon atoms, an aryl group having 6 to 10 carbon atoms, an aralkyl group having 7 to 10 carbon atoms, a halogen group such as a chloro group and a bromo group, a silyl group having 1 to 6 carbon atoms, a sulfonic acid group and a salt thereof (sodium salt, etc.), and the like.
[0099] Specifically, examples include, but are not limited to, aromatic dicarboxylic acids having 8 to 20 carbon atoms that are unsubstituted or substituted with a predetermined substituent, such as terephthalic acid, naphthalene dicarboxylic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, and 5-sodium sulfoisophthalic acid. Among them, terephthalic acid is preferred.
[0100] The aromatic dicarboxylic acid constituting the aromatic dicarboxylic acid unit may be used alone or in combination of two or more.
[0101] (Aliphatic dicarboxylic acid unit)
[0102] Examples of the aliphatic dicarboxylic acid constituting the aliphatic dicarboxylic acid unit include, but are not limited to, linear or branched saturated aliphatic dicarboxylic acids having 3 to 20 carbon atoms, such as malonic acid, dimethylmalonic acid, succinic acid, 2,2-dimethylsuccinic acid, 2,3-dimethylglutaric acid, 2,2-diethylsuccinic acid, 2,3-diethylglutaric acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid, and diglycolic acid.
[0103] (alicyclic dicarboxylic acid unit)
[0104] Examples of the alicyclic dicarboxylic acid constituting the alicyclic dicarboxylic acid unit (hereinafter also referred to as "alicyclic dicarboxylic acid unit") include, but are not limited to, alicyclic dicarboxylic acids having 3 to 10 carbon atoms in the alicyclic structure. Preferably, the alicyclic dicarboxylic acid has 5 to 10 carbon atoms in the alicyclic structure.
[0105] Examples of such alicyclic dicarboxylic acids include, but are not limited to, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid. Among them, 1,4-cyclohexanedicarboxylic acid is preferred.
[0106] In addition, the alicyclic dicarboxylic acid which comprises an alicyclic dicarboxylic acid unit may be used individually or in combination of 2 or more types.
[0107] The alicyclic group of the alicyclic dicarboxylic acid may be unsubstituted or may have a substituent. Examples of the substituent include, but are not limited to, alkyl groups having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl.
[0108] By using such a dicarboxylic acid, the mechanical properties of the polyamide composition, particularly water absorption rigidity, thermal rigidity, fluidity, surface appearance, corrosion resistance, etc., tend to be more excellent.
[0109] In the polyamide composition of the present embodiment, the dicarboxylic acid constituting the dicarboxylic acid unit (A-2a) is not limited to the compounds described above as the dicarboxylic acids, and may be a compound equivalent to the above dicarboxylic acids.
[0110] Here, the "compound equivalent to a dicarboxylic acid" refers to a compound that can form a dicarboxylic acid structure similar to the dicarboxylic acid structure derived from the above dicarboxylic acid. Examples of such compounds include, but are not limited to, anhydrides and halides of dicarboxylic acids.
[0111] The (A-2) amorphous polyamide may further contain a unit derived from a trivalent or higher polyvalent carboxylic acid such as trimellitic acid, trimesic acid, and pyromellitic acid, as required.
[0112] The trivalent or higher polyvalent carboxylic acid may be used alone or in combination of two or more.
[0113] [(A-2b) diamine unit]
[0114] The diamine unit (A-2b) constituting the amorphous polyamide (A-2) preferably contains at least 50 mol % of a diamine unit having a carbon number of 4 to 10. Examples thereof include, but are not limited to, aliphatic diamine units, alicyclic diamine units, and aromatic diamine units.
[0115] (Aliphatic diamine unit)
[0116] Examples of the aliphatic diamine constituting the aliphatic diamine unit include, but are not limited to, linear saturated aliphatic diamines having 2 to 20 carbon atoms, such as ethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, and tridecamethylenediamine.
[0117] (Alicyclic diamine unit)
[0118] Examples of the alicyclic diamine (hereinafter also referred to as “alicyclic diamine”) constituting the alicyclic diamine unit include 1,4-cyclohexanediamine, 1,3-cyclohexanediamine, and 1,3-cyclopentanediamine, but are not limited thereto.
[0119] (Aromatic diamine unit)
[0120] The aromatic diamine constituting the aromatic diamine unit may be any diamine containing an aromatic group, and examples thereof include, but are not limited to, meta-xylylenediamine.
[0121] Among them, an aliphatic diamine unit is preferred, a diamine unit having a linear saturated aliphatic group having 4 to 10 carbon atoms is more preferred, a diamine unit having a linear saturated aliphatic group having 6 to 10 carbon atoms is further preferred, and a hexamethylenediamine unit is particularly preferred.
[0122] By using such a diamine, there is a tendency to obtain a polyamide composition having more excellent mechanical properties, particularly water absorption rigidity, thermal rigidity, fluidity, surface appearance, corrosiveness, and the like.
[0123] In addition, the diamine may be used alone or in combination of two or more.
[0124] As the amorphous polyamide (A-2), polyamide 6I, 6I / 6T, 9I or 10I is preferred, polyamide 6I or 6I / 6T is more preferred, and polyamide 6I is most preferred.
[0125] The amorphous polyamide (A-2) may further contain a trivalent or higher-valent aliphatic amine such as bis-hexamethylenetriamine, as necessary.
[0126] The trivalent or higher polyvalent aliphatic amines may be used alone or in combination of two or more.
[0127] [At least one unit selected from the group consisting of lactam units and aminocarboxylic acid units]
[0128] (A-2) The amorphous polyamide may further contain at least one unit selected from the group consisting of a lactam unit and an aminocarboxylic acid unit. By containing such a unit, there is a tendency to obtain a polyamide with better toughness. It should be noted that, herein, the lactam and aminocarboxylic acid constituting the lactam unit and the aminocarboxylic acid unit refer to lactam and aminocarboxylic acid that can be polymerized (polycondensed).
[0129] As lactams and aminocarboxylic acids constituting the lactam unit and the aminocarboxylic acid unit, for example, lactams and aminocarboxylic acids having 4 to 14 carbon atoms are preferred, and lactams and aminocarboxylic acids having 6 to 12 carbon atoms are more preferred, but are not limited thereto.
[0130] Examples of the lactam constituting the lactam unit include butyrolactam, pivalolactam, ε-caprolactam, capryllactam, enantholactam, undecanolactam, and laurolactam (laurolactam), but are not limited thereto.
[0131] Among them, as the lactam, ε-caprolactam or laurolactam is preferred, and ε-caprolactam is more preferred. By containing such a lactam, there is a tendency for the polyamide composition to have better toughness.
[0132] Examples of the aminocarboxylic acid constituting the aminocarboxylic acid unit include, but are not limited to, ω-aminocarboxylic acids and α,ω-amino acids which are compounds obtained by ring-opening of lactams.
[0133] As the aminocarboxylic acid, a linear or branched saturated aliphatic carboxylic acid having 4 to 14 carbon atoms substituted with an amino group at the ω position is preferred. Examples of such aminocarboxylic acids include, but are not limited to, 6-aminocaproic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid. In addition, examples of aminocarboxylic acids include p-aminomethylbenzoic acid.
[0134] The lactam and aminocarboxylic acid constituting the lactam unit and the aminocarboxylic acid unit may be used alone or in combination of two or more.
[0135] The total ratio (mol %) of the lactam unit and the aminocarboxylic acid unit to the entire polyamide is preferably 0 mol % to 20 mol %, more preferably 0 mol % to 10 mol %, further preferably 0 mol % to 5 mol %.
[0136] When the total ratio of the lactam unit and the aminocarboxylic acid unit is within the above range, there is a tendency that effects such as improvement in fluidity can be obtained.
[0137] [(A-2) Characteristics of amorphous polyamide]
[0138] ((A-2) Weight average molecular weight Mw of amorphous polyamide)
[0139] As an index of the molecular weight of the (A-2) non-crystalline polyamide, the weight average molecular weight (Mw) of the (A-2) non-crystalline polyamide can be used.
[0140] The weight average molecular weight (Mw) of the amorphous polyamide (A-2) is preferably 10,000 to 35,000, more preferably 10,000 to 33,000, further preferably 13,000 to 30,000, further preferably 15,000 to 29,000, particularly preferably 18,000 to 27,000, and most preferably 19,000 to 21,000.
[0141] When the weight average molecular weight (Mw) of the amorphous polyamide (A-2) is within the above range, a polyamide composition having more excellent mechanical properties, particularly water absorption rigidity, thermal rigidity, and flame retardancy can be obtained. In addition, a molded article obtained from the polyamide composition containing components represented by an inorganic filler has a more excellent surface appearance.
[0142] In order to reduce the number average particle size of the crystal domains in the (A-1) crystalline polyamide, it is preferable to improve the physical kneading efficiency. By making the melt viscosities in the molten state close, the number average particle size can be reduced.
[0143] The (A-2) amorphous polyamide containing an aromatic compound unit in the molecular structure of the polyamide has a high melt viscosity when the molecular weight is the same as that of the (A) crystalline polyamide. Therefore, the molecular weight of the (A-2) amorphous polyamide is preferably smaller than that of the (A-1) crystalline polyamide.
[0144] The weight average molecular weight (Mw) of the (A-2) amorphous polyamide can be measured using GPC.
[0145] ((A-2) Molecular weight distribution of amorphous polyamide)
[0146] The molecular weight distribution of the (A-2) amorphous polyamide is determined by dividing the weight average molecular weight (Mw) of the (A-2) amorphous polyamide by the number average molecular weight (Mn) of the (A-2) amorphous polyamide, Mw / Mn, as an index.
[0147] Mw / Mn is preferably 1.0 to 2.6, more preferably 1.3 to 2.5, further preferably 1.5 to 2.5, particularly preferably 1.8 to 2.4, and most preferably 2.0 to 2.4.
[0148] When Mw / Mn is within the above range, a polyamide composition having better moldability and appearance can be obtained. In addition, a molded article obtained from a polyamide composition containing components represented by an inorganic filler has better surface appearance.
[0149] Examples of a method for controlling Mw / Mn within the above range include the method described in 1) or 2) below.
[0150] 1) A method of adding a known polycondensation catalyst such as phosphoric acid or sodium hypophosphite as an additive during hot melt polymerization of polyamide.
[0151] 2) In addition to the method 1) above, a method in which the polymerization conditions such as heating conditions and reduced pressure conditions are controlled to complete the polycondensation reaction at the lowest possible temperature and in the shortest possible time.
[0152] When aromatic compound units are contained in the molecular structure of polyamide, the molecular weight distribution (Mw / Mn) tends to increase as the molecular weight increases. A high molecular weight distribution means that the ratio of polyamide molecules with a three-dimensional molecular structure is high. By reducing the ratio of polyamide molecules with a three-dimensional structure, the compatibility with the (A-1) crystalline polyamide can be improved, and the number average particle size of the crystal domain can be reduced. Therefore, by controlling Mw / Mn within the above range, the three-dimensional structuralization of the molecules can be suppressed during high-temperature processing, and a polyamide composition with excellent fluidity, better welding strength and product appearance can be obtained. In addition, the surface appearance of the molded product obtained from the polyamide composition containing components represented by inorganic fillers is more excellent.
[0153] In addition, Mw / Mn can be calculated using Mw and Mn obtained by GPC.
[0154] ((A-2) Crystallization enthalpy ΔH of amorphous polyamide)
[0155] From the viewpoint of appearance, the crystallization enthalpy ΔH of the amorphous polyamide (A-2) is preferably less than 15 J / g, more preferably 10 J / g or less, further preferably 5 J / g or less, and particularly preferably 0 J / g.
[0156] As a method for controlling the crystallization enthalpy ΔH of the amorphous polyamide (A-2) within the above range, a known method for reducing the crystallinity of the polyamide can be used without particular limitation. As a known method for reducing the crystallinity of the polyamide, specifically, for example, there can be mentioned: a method of increasing the ratio of the meta-substituted aromatic dicarboxylic acid unit relative to the dicarboxylic acid unit, and a method of increasing the ratio of the meta-substituted aromatic diamine unit relative to the diamine unit. From this viewpoint, in the amorphous polyamide (A-2), as the dicarboxylic acid unit (A-2a), it is preferred that 50 mol% or more of the isophthalic acid unit is contained in all the dicarboxylic acid units constituting the amorphous polyamide (A-2), more preferably 75 mol% or more of the isophthalic acid unit is contained, and even more preferably 100 mol% of the isophthalic acid unit is contained.
[0157] (A-2) The crystallization enthalpy ΔH of the amorphous polyamide can be measured, for example, in accordance with JIS-K7121 using a measuring device such as Diamond-DSC manufactured by PERKIN-ELMER.
[0158] [(A-2) Amorphous Polyamide Content]
[0159] In the polyamide composition of the present embodiment, the content of the amorphous polyamide (A-2) can be set to, for example, 1.0 mass % to 60.0 mass %, can be set to 3.0 mass % to 40.0 mass %, can be set to 5.0 mass % to 30.0 mass %, can be set to 7.0 mass % to 25.0 mass %, relative to the total mass of the polyamide composition.
[0160] <Capping Agent>
[0161] At least one polyamide selected from the group consisting of (A-1) crystalline polyamides and (A-2) amorphous polyamides has a terminal blocked with a terminal blocking agent.
[0162] When polyamide is produced from the above-mentioned dicarboxylic acid and diamine and, if necessary, at least one compound selected from the group consisting of lactam and aminocarboxylic acid, such a terminal blocking agent can be added as a molecular weight modifier.
[0163] Examples of the terminal blocking agent include, but are not limited to, monocarboxylic acids, monoamines, acid anhydrides, monoisocyanates, monoacyl halides, monoesters, and monoalcohols. Examples of the acid anhydride include phthalic anhydride.
[0164] Among them, monocarboxylic acid or monoamine is preferred. When the ends of the polyamide are blocked with an end blocking agent, a polyamide composition tends to have better thermal stability.
[0165] The blocking agent may be used alone or in combination of two or more.
[0166] The monocarboxylic acid that can be used as the end-capping agent can be any monocarboxylic acid that is reactive with the amino group that may be present at the end of the polyamide. Specifically, examples of the monocarboxylic acid include, but are not limited to, aliphatic monocarboxylic acids, alicyclic monocarboxylic acids, and aromatic monocarboxylic acids.
[0167] Examples of the aliphatic monocarboxylic acid include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, neopentanoic acid, and isobutyric acid, but are not limited thereto.
[0168] Examples of the alicyclic monocarboxylic acid include cyclohexanecarboxylic acid, but are not limited thereto.
[0169] Examples of the aromatic monocarboxylic acid include benzoic acid, toluic acid, α-naphthoic acid, β-naphthoic acid, methylnaphthoic acid, and phenylacetic acid, but are not limited thereto.
[0170] These monocarboxylic acids may be used alone or in combination of two or more.
[0171] The monoamine that can be used as the end-capping agent may be any monoamine that is reactive with a carboxyl group that may be present at the end of the polyamide. Specific examples of the monoamine include, but are not limited to, aliphatic monoamines, alicyclic monoamines, and aromatic monoamines.
[0172] Examples of the aliphatic monoamine include methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine, but the aliphatic monoamine is not limited thereto.
[0173] Examples of the alicyclic monoamine include cyclohexylamine and dicyclohexylamine, but are not limited thereto.
[0174] Examples of the aromatic monoamine include aniline, toluidine, diphenylamine, naphthylamine, and the like, but are not limited thereto.
[0175] These monoamines may be used alone or in combination of two or more.
[0176] A polyamide composition containing a polyamide end-capped with an end-capping agent tends to be excellent in heat resistance, fluidity, toughness, low water absorption, rigidity, corrosion resistance, moldability, and appearance.
[0177] <Production Method of Polyamide>
[0178] When obtaining each polyamide ((A-1) crystalline polyamide and (A-2) amorphous polyamide), the amount of dicarboxylic acid added and the amount of diamine added are preferably approximately equimolar. Regarding the molar ratio, taking into account the amount of diamine released to the outside of the reaction system during the polymerization reaction, the molar amount of all diamines is preferably 0.9 to 1.2, more preferably 0.95 to 1.1, and even more preferably 0.98 to 1.05, relative to the molar amount of all dicarboxylic acids.
[0179] The method for producing polyamide includes, for example, the following polymerization step (1) or (2), but is not limited thereto.
[0180] (1) A step of polymerizing a combination of a dicarboxylic acid constituting a dicarboxylic acid unit and a diamine constituting a diamine unit to obtain a polymer.
[0181] (2) A step of polymerizing one or more selected from the group consisting of lactam constituting a lactam unit and aminocarboxylic acid constituting an aminocarboxylic acid unit to obtain a polymer.
[0182] In addition, as a method for producing polyamide, it is preferred that a step of increasing the degree of polymerization of the polyamide is further included after the polymerization step. In addition, an end-capping step of capping the ends of the obtained polymer with an end-capping agent may be included after the polymerization step and the increase step as required.
[0183] As a specific method for producing polyamide, various methods exemplified in the following 1) to 4) are mentioned, for example.
[0184] 1) A method in which an aqueous solution or aqueous suspension of at least one selected from the group consisting of a dicarboxylic acid-diamine salt, a mixture of a dicarboxylic acid and a diamine, a lactam, and an aminocarboxylic acid is heated to polymerize while maintaining the molten state (hereinafter sometimes referred to as "hot melt polymerization method").
[0185] 2) A method in which the degree of polymerization of a polyamide obtained by a hot melt polymerization method is increased while the polyamide is kept in a solid state at a temperature below the melting point (hereinafter, sometimes referred to as a “hot melt polymerization / solid phase polymerization method”).
[0186] 3) A method of polymerizing one or more selected from the group consisting of dicarboxylic acid-diamine salts, mixtures of dicarboxylic acids and diamines, lactams, and aminocarboxylic acids while maintaining a solid state (hereinafter sometimes referred to as “solid phase polymerization”).
[0187] 4) A method of polymerizing using a dicarboxylic acid halide component equivalent to a dicarboxylic acid and a diamine component (hereinafter, sometimes referred to as a “solution method”).
[0188] Among them, as a specific method for producing polyamide, a method for producing polyamide by hot melt polymerization is preferably used. In addition, when producing polyamide by hot melt polymerization, it is preferred to keep the molten state until the polymerization is completed. In order to keep the molten state, it is necessary to produce under polymerization conditions suitable for polyamide. As polymerization conditions, for example, the following conditions can be cited. First, the polymerization pressure in the hot melt polymerization method is controlled to 14 kg / cm 2 Above and 25kg / cm 2 Next, the pressure in the tank was reduced over 30 minutes until it reached atmospheric pressure (gauge pressure = 0 kg / cm 2 ).
[0189] In the method for producing polyamide, the polymerization method is not particularly limited, and may be a batch method or a continuous method.
[0190] The polymerization apparatus used for the production of polyamide is not particularly limited, and a known apparatus can be used. Specific examples of the polymerization apparatus include autoclave reactors, drum reactors, extruder reactors (kneaders, etc.), and the like.
[0191] Hereinafter, as a method for producing polyamide, a method for producing polyamide by a batch hot melt polymerization method will be specifically described, but the method for producing polyamide is not limited thereto.
[0192] First, an aqueous solution containing about 40% by mass or more and about 60% by mass or less of raw material components of polyamide (a combination of dicarboxylic acid and diamine, and at least one selected from the group consisting of lactam and aminocarboxylic acid as required) is prepared. Next, the aqueous solution is concentrated to about 65% by mass or more and about 90% by mass or less in a concentration tank operated at a temperature of 110° C. or more and 180° C. or less and a pressure of about 0.035 MPa or more and about 0.6 MPa or less (gauge pressure) to obtain a concentrated solution.
[0193] Next, the obtained concentrated solution was transferred to an autoclave, and heating was continued until the pressure in the autoclave reached about 1.2 MPa or more and about 2.2 MPa or less (gauge pressure).
[0194] Next, in the autoclave, the pressure is maintained at about 1.2 MPa or more and about 2.2 MPa or less (gauge pressure) while extracting at least one of the water and gas components. Next, when the temperature reaches about 220°C or more and about 260°C or less, the pressure is reduced to atmospheric pressure (gauge pressure is 0 MPa). After the pressure in the autoclave is reduced to atmospheric pressure, the pressure is reduced as needed, thereby effectively removing water generated as a by-product.
[0195] Next, the autoclave is pressurized with an inert gas such as nitrogen, and the polyamide melt is extruded from the autoclave in the form of strands. The extruded strands are cooled and cut to obtain polyamide pellets.
[0196] <Polymer terminal of polyamide>
[0197] The polymer terminals of the polyamide ((A-1) crystalline polyamide and (A-2) amorphous polyamide) contained in the polyamide composition of the present embodiment are not particularly limited, but can be classified into the following 1) to 4) and defined.
[0198] That is, 1) amino terminal, 2) carboxyl terminal, 3) terminal formed by a blocking agent, and 4) other terminal.
[0199] 1) The amino terminus is a polymer terminus having an amino group (-NH2 group) derived from a diamine.
[0200] 2) The carboxyl terminal is a polymer terminal having a carboxyl group (-COOH group) and is derived from a dicarboxylic acid.
[0201] 3) The terminal formed by the terminal blocking agent is a terminal formed when the terminal blocking agent is added during polymerization. Examples of the terminal blocking agent include the above-mentioned terminal blocking agents.
[0202] 4) Other terminals are polymer terminals not classified into the above 1) to 3). Specific examples of other terminals include terminals generated by deamination reaction of an amino terminal and terminals generated by decarboxylation reaction of a carboxyl terminal.
[0203] 《(B)Phosphorus-containing flame retardants》
[0204] The phosphorus-containing flame retardant (B) is not particularly limited as long as it contains phosphorus and does not contain halogen elements. Examples of the phosphorus-containing flame retardant include phosphate flame retardants, polyphosphate melamine flame retardants, phosphazene flame retardants, phosphinic acid flame retardants, and red phosphorus flame retardants.
[0205] Among them, as the phosphorus-containing flame retardant, a phosphate flame retardant, a polyphosphate melamine flame retardant, a phosphazene flame retardant or a phosphinic acid flame retardant is preferred, and a phosphinic acid flame retardant is particularly preferred.
[0206] Specifically, the phosphinic acid flame retardant may include, for example, at least one phosphinic acid salt selected from the group consisting of a phosphinic acid salt represented by the following general formula (1) (hereinafter, sometimes referred to as “phosphinic acid salt (1)”), a diphosphinic acid salt represented by the following general formula (2) (hereinafter, sometimes referred to as “diphosphinic acid salt (2)”), and condensates thereof, and a complex salt of a phosphinic acid salt and a phosphonic acid salt represented by the following general formula (3).
[0207]
[0208] (In general formula (1), R 11 and R 12 Each independently represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. n11+ is a metal ion with a valence of n11. M is an element belonging to Group 2 or Group 15 of the Periodic Table, a transition element, zinc or aluminum. n11 is 2 or 3. In the case where n11 is 2 or 3, the presence of multiple R 11 and multiple R 12 Each may be the same or different.
[0209] In general formula (2), R 21 and R 22 Each is independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. 21M' is an alkylene group having 1 to 10 carbon atoms or an arylene group having 6 to 10 carbon atoms. m21+ is a metal ion with a valence of m21. M' is an element belonging to Group 2 or Group 15 of the Periodic Table, a transition element, zinc or aluminum. n21 is an integer greater than 1 and less than 3. When n21 is 2 or 3, the presence of multiple R 21 , multiple R 22 and multiple Y 21 Each may be the same or different. m21 is 2 or 3. x is 1 or 2. When x is 2, the multiple M's present may be the same or different. n21, x and m21 are integers satisfying the relationship 2×n21=m21×x.
[0210] [R 11 , R 12 , R 21 , R 22 , R1, R2 and R3]
[0211] R 11 , R 12 , R 21 , R 22 , R1, R2 and R3 are each independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. When n11 is 2 or 3, the presence of multiple R 11 and multiple R 12 Each may be the same or different, but is preferably the same from the perspective of ease of manufacture. 21 and multiple R 22 The respective ones may be the same or different, but are preferably the same from the viewpoint of easy production.
[0212] The alkyl group may be chain-shaped or cyclic, but is preferably chain-shaped. The chain-shaped alkyl group may be straight-chain or branched. Examples of the straight-chain alkyl group include methyl, ethyl, n-propyl, n-butyl, n-pentyl, and n-hexyl. Examples of the branched alkyl group include 1-methylethyl, 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 3,3-dimethylbutyl, 1-ethylbutyl, 2-ethylbutyl, and 1,1,2-trimethylpropyl.
[0213] Examples of the aryl group include a phenyl group and a naphthyl group.
[0214] The alkyl group and the aryl group may have a substituent. Examples of the substituent of the alkyl group include an aryl group having 6 to 10 carbon atoms. Examples of the substituent of the aryl group include an alkyl group having 1 to 6 carbon atoms.
[0215] Specific examples of the alkyl group having a substituent include a benzyl group and the like.
[0216] Specific examples of the aryl group having a substituent include a tolyl group and a xylyl group.
[0217] Among them, as R 11 , R 12 , R 21 and R 22 , preferably an alkyl group having 1 to 6 carbon atoms, more preferably a methyl group or an ethyl group.
[0218] [Y 21 ]
[0219] Y 21 is an alkylene group having 1 to 10 carbon atoms or an arylene group having 6 to 10 carbon atoms. 21 The respective ones may be the same or different, but are preferably the same from the viewpoint of easy production.
[0220] The alkylene group may be chain-shaped or cyclic, but is preferably chain-shaped. The chain-shaped alkylene group may be straight-chain or branched. Examples of straight-chain alkylene groups include methylene, ethylene, trimethylene, tetramethylene, pentamethylene, and hexamethylene. Examples of branched alkylene groups include 1-methylethylene and 1-methylpropylene.
[0221] As an arylene group, a phenylene group, a naphthylene group, etc. are mentioned, for example.
[0222] The alkylene group and the arylene group may have a substituent. Examples of the substituent of the alkylene group include an aryl group having 6 to 10 carbon atoms. Examples of the substituent of the arylene group include an alkyl group having 1 to 6 carbon atoms.
[0223] Specific examples of the alkylene group having a substituent include a phenylmethylene group, a phenylethylene group, a phenyltrimethylene group, and a phenyltetramethylene group.
[0224] Specific examples of the arylene group having a substituent include a methylphenylene group, an ethylphenylene group, a tert-butylphenylene group, a methylnaphthylene group, an ethylnaphthylene group, and a tert-butylnaphthylene group.
[0225] Among them, as Y 21 , preferably an alkylene group having 1 to 10 carbon atoms, more preferably a methylene group or an ethylene group.
[0226] [M and M']
[0227] M and M' are each independently an ion of an element belonging to Group 2 or Group 15 of the periodic table, an ion of a transition element, a zinc ion or an aluminum ion. Examples of ions of elements belonging to Group 2 of the periodic table include calcium ions and magnesium ions. Examples of ions of elements belonging to Group 15 of the periodic table include bismuth ions and the like.
[0228] When x is 2, a plurality of M's present may be the same or different, but are preferably the same from the viewpoint of ease of production.
[0229] Among them, as M and M', calcium, zinc or aluminum is preferred, and calcium or aluminum is more preferred.
[0230] [x]
[0231] x represents the number of M', and is 1 or 2. x can be appropriately selected according to the type of M' and the number of diphosphinic acids.
[0232] [n11 and n21]
[0233] n11 represents the number of phosphinic acids and the valence of M, and is 2 or 3. n11 can be appropriately selected according to the type and valence of M.
[0234] n21 represents the number of diphosphinic acids, and is an integer of 1 to 3. n21 can be appropriately selected according to the type and number of M'.
[0235] [m21]
[0236] m21 represents the valence of M', which is 2 or 3.
[0237] n21, x and m21 are integers satisfying the relationship 2×n21=m21×x.
[0238] Specific examples of the preferred phosphinate (1) include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate. Among them, calcium diethylphosphinate or aluminum diethylphosphinate is particularly preferred as the phosphinate (1) from the viewpoint of excellent flame retardancy.
[0239] Specific examples of preferred diphosphinates (2) include calcium methanedi(methylphosphinate), magnesium methanedi(methylphosphinate), aluminum methanedi(methylphosphinate), zinc methanedi(methylphosphinate), calcium benzene-1,4-di(methylphosphinate), magnesium benzene-1,4-di(methylphosphinate), aluminum benzene-1,4-di(methylphosphinate), zinc benzene-1,4-di(methylphosphinate), and the like.
[0240] As the manufacture method of phosphinates, there is no particular restriction, for example, the method of recording in Japanese Unexamined Patent Application No. 2005-179362, European Patent Application Publication No. 699708 and Japanese Unexamined Patent Application No. 08-073729 etc. can be enumerated. Specifically, phosphinic acid and metal carbonate, metal hydroxide or metal oxide are used to manufacture in aqueous solution. These phosphinates are essentially monomeric compounds, but depend on reaction conditions, and also include polymeric phosphinates as condensation products with a condensation degree of more than 1 and less than 3 according to environment.
[0241] Specific commercial products of the phosphinate include, for example, "Exolit OP1230", "Exolit OP1240", "Exolit OP1312", "Exolit OP1314", and "Exolit OP1400" manufactured by Clariant; and "HR8900", "MADP8900SP", "MADP8900BS", and "HR8966" manufactured by Weihai Hairun Corporation.
[0242] Among phosphinates, a flame retardant represented by chemical formula (3) which is a complex salt of a phosphinate and a phosphonate is more preferred from the viewpoint of heat resistance and flame retardancy.
[0243]
[0244] The most preferred flame retardant is a flame retardant represented by a hexavalent anion having R1=ethyl, R2=ethyl, R3=ethyl, a=4, b=1 and a hexavalent cation having two M=aluminum and m=3 in formula (3). Specific commercial examples include "HR8900", "MADP8900SP", "MADP8900BS" and "HR8966" manufactured by Weihai Hairun Company.
[0245] <(C) Polyamide elastomer>
[0246] (C) Polyamide elastomers preferably have polyamide units as hard segments and polyether units as soft segments, and examples thereof include polyetheresteramide elastomers in which hard segments and soft segments are bonded via ester bonds and polyetheramide elastomers in which hard segments and soft segments are bonded via amide bonds.
[0247] The hard segment can be derived from a polyamide having carboxyl groups at both ends, and is a segment comprising a polyamide-forming unit and at least one dicarboxylic acid selected from the group consisting of aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and aromatic dicarboxylic acids.
[0248] The polyamide forming unit in the hard segment includes lactam, aminocarboxylic acid and / or diamine and dicarboxylic acid (nylon salt), and examples thereof include units obtained by reacting one or more selected from the group consisting of lactam, aminocarboxylic acid, and diamine and dicarboxylic acid (nylon salt).
[0249] Examples of lactams include aliphatic lactams having 5 to 20 carbon atoms, such as ε-caprolactam, ω-enantholactam, ω-undecanolactam, ω-laurolactam, and 2-pyrrolidone. Examples of aminocarboxylic acids include aliphatic ω-aminocarboxylic acids having 5 to 20 carbon atoms, such as 6-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 10-aminodecanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid. Examples of the diamine include diamine compounds such as aliphatic diamines having 2 to 20 carbon atoms, such as ethylenediamine, trimethylenediamine, tetramethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexane-1,6-diamine, 2,4,4-trimethylhexane-1,6-diamine, and 3-methylpentane-1,5-diamine.
[0250] Among them, ε-caprolactam is preferred from the viewpoint of heat resistance, chemical resistance and mechanical properties.
[0251] The number average molecular weight of the hard segment is preferably 200 to 15,000, and more preferably 300 to 10,000 from the viewpoint of flexibility and moldability.
[0252] The soft segment is preferably a polyether, for example, preferably based on at least one C2-C5 polyoxyalkylene unit, particularly preferably a unit selected from the group consisting of ethylene oxide, propylene oxide, tetrahydrofuran and mixtures thereof. The number average molecular weight of the soft segment is preferably 200-6000, more preferably 400-3000.
[0253] The melting point (Tm) of the polyamide elastomer is 160.0°C or higher, preferably 230.0°C or lower, more preferably 180.0°C or higher and 220.0°C or lower, particularly preferably 190.0°C or higher and 210.0°C or lower.
[0254] When the melting point Tm of the polyamide elastomer is within the above range, the polyamide composition can be excellent in melt processing such as extrusion and molding, and can further suppress thermal decomposition of the phosphorus-containing flame retardant, and has an excellent deflection temperature under load.
[0255] The content of the polyamide (A) is preferably 20% by mass to 60% by mass, more preferably 30% by mass to 60% by mass, further preferably 40% by mass to 60% by mass, and most preferably 50% by mass to 60% by mass, relative to the total mass of the polyamide composition.
[0256] The content of the (C) polyamide elastomer is preferably 2% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 15% by mass or less, based on the total mass of the polyamide composition.
[0257] The content of the phosphorus-containing flame retardant is preferably 10% by mass to 30% by mass, more preferably 12% by mass to 25% by mass, particularly preferably 14% by mass to 20% by mass, based on the total mass of the polyamide composition.
[0258] By setting the content of the phosphorus-containing flame retardant to be above the lower limit, a polyamide composition with better flame retardancy can be obtained. On the other hand, by setting the amount of the phosphorus-containing flame retardant to be below the upper limit, a polyamide composition with better flame retardancy can be obtained without impairing the properties of the polyamide.
[0259] 《(D)Inorganic filling materials》
[0260] The polyamide composition of the present embodiment may further contain (D) an inorganic filler in addition to the above-mentioned (A) to (C) components.
[0261] As inorganic filler, for example, glass fiber, carbon fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, clay, flaky glass, talc, kaolin, mica, hydrotalcite, calcium carbonate, magnesium carbonate, zinc carbonate, zinc oxide, calcium hydrogen phosphate, wollastonite, silicon dioxide, zeolite, aluminum oxide, boehmite, aluminum hydroxide, titanium oxide, silicon oxide, magnesium oxide, calcium silicate, sodium aluminosilicate, magnesium silicate, Ketjen black, acetylene black, furnace black, carbon nanotube, graphite, brass, copper, silver, aluminum, nickel, iron, calcium fluoride, montmorillonite, swelling fluorine mica, apatite, etc., but not limited to this. These inorganic fillers can be used alone or in combination of two or more.
[0262] Among them, from the viewpoint of further improving mechanical strength, it is preferred to select at least one of the group consisting of glass fiber, carbon fiber, wollastonite, kaolin, mica, talc, calcium carbonate, magnesium carbonate, potassium titanate fiber, aluminum borate fiber and clay. In addition, among them, it is more preferred to select at least one of the group consisting of glass fiber, carbon fiber, wollastonite, kaolin, mica, talc, calcium carbonate and clay. Glass fiber is most preferred.
[0263] When the inorganic filler is glass fiber or carbon fiber, the number average fiber diameter (d) is preferably 3 μm or more and 30 μm or less, more preferably 3 μm or more and 20 μm or less, further preferably 3 μm or more and 12 μm or less, particularly preferably 3 μm or more and 9 μm or less, and most preferably 4 μm or more and 6 μm or less.
[0264] When the number average fiber diameter is below the upper limit, a polyamide composition having better toughness and surface appearance of a molded product can be obtained. On the other hand, when the number average fiber diameter is above the lower limit, a polyamide composition having better balance between cost and powder handling and physical properties (fluidity, etc.) can be obtained. In addition, when the number average fiber diameter is 3 μm or more and 9 μm or less, a polyamide composition having better vibration fatigue characteristics and sliding properties can be obtained.
[0265] When the inorganic filler is glass fiber or carbon fiber, its cross section may be a perfect circle or a flat shape. Examples of the flat cross section include, but are not limited to, a rectangular shape, an oblong shape close to a rectangular shape, an elliptical shape, and a cocoon shape with a tapered center in the long side direction. Here, the "flattening ratio" in this specification refers to the value represented by d2 / d1 when the major diameter of the fiber cross section is set to d2 and the minor diameter of the fiber cross section is set to d1 (the flattening ratio of a perfect circle is about 1).
[0266] When the inorganic filler is glass fiber or carbon fiber, from the viewpoint of being able to impart excellent mechanical strength to the polyamide composition, the number average fiber diameter (d) is preferably 3 μm or more and 30 μm or less, the weight average fiber length (l) is preferably 100 μm or more and 750 μm or less, and the ratio of the weight average fiber length (l) to the number average fiber diameter (d), i.e., the aspect ratio (l / d), is preferably 10 or more and 100 or less. It should be noted that the "number average fiber diameter (d)" referred to herein is the average value of the major diameter (the above-mentioned d2) of the fiber cross section, and is obtained using the calculation method described below.
[0267] In addition, from the viewpoint of reducing the warpage of the plate-shaped molded product and improving the heat resistance, toughness, low water absorption and heat aging resistance, the flatness is preferably 1.5 or more, more preferably 1.5 or more and 10.0 or less, further preferably 2.5 or more and 10.0 or less, particularly preferably greater than 3.0 and less than or equal to 6.0, and most preferably 3.1 or more and 6.0 or less. When the flatness is within the above range, it is possible to more effectively prevent breakage during mixing, kneading, molding and other processes with other components, and the desired effect can be more fully obtained for the molded product.
[0268] Regarding the thickness of glass fiber and carbon fiber with a flatness of 1.5 or more, it is preferred that the short diameter d1 of the fiber cross section is 0.5 μm or more and 25 μm or less and the long diameter d2 of the fiber cross section is 1.25 μm or more and 250 μm or less, but not limited thereto. It is more preferred that the short diameter d1 of the fiber cross section is 3.0 μm or more and 25 μm or less and the long diameter d2 of the fiber cross section is 1.25 μm or more and 250 μm or less. By keeping the short diameter (d1) and the long diameter (d2) within the above range, the difficulty of spinning the fiber can be more effectively avoided, and the strength of the molded product can be further improved without reducing the contact area with the resin (polyamide).
[0269] As for glass fibers and carbon fibers having an oblateness of 1.5 or more, it is preferred to use glass fibers having an oblateness of 1.5 or more produced by using a perforated plate having a plurality of holes on the bottom surface and provided with flanges surrounding the plurality of hole outlets and extending downward from the bottom surface, or a nozzle head for spinning special-shaped glass fibers provided with a plurality of flanges extending downward from the front end of the outer peripheral portion of a nozzle head having one or more holes. These fibrous reinforcing materials may be used directly in the form of a roving, or may be used in the form of chopped glass strands after further cutting.
[0270] In addition, the "number average fiber diameter (d)" and "weight average fiber length (l)" in this specification can be obtained by the following method. First, the polyamide composition is placed in an electric furnace to incinerate the organic matter contained therein. More than 100 glass fibers (or carbon fibers) are randomly selected from the residue components after the treatment, and the fiber diameters (long diameters) of these glass fibers (or carbon fibers) are measured by a scanning electron microscope (SEM), thereby obtaining the number average fiber diameter. In addition, the fiber length is measured using an SEM photograph of the above-mentioned 100 or more glass fibers (or carbon fibers) taken at a magnification of 1000 times, thereby obtaining the weight average fiber length.
[0271] In addition, the glass fiber or the carbon fiber may be surface-treated with a silane coupling agent or the like.
[0272] Examples of the silane coupling agent include aminosilanes, mercaptosilanes, epoxysilanes, and vinylsilanes, but the silane coupling agent is not limited thereto.
[0273] Examples of the aminosilanes include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.
[0274] As mercaptosilanes, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, etc. are mentioned, for example.
[0275] These silane coupling agents may be used alone or in combination of two or more.
[0276] Among them, aminosilanes are preferred as the silane coupling agent.
[0277] In addition, the glass fibers or carbon fibers may further contain a sizing agent.
[0278] Examples of the sizing agent include copolymers containing unsaturated vinyl monomers containing carboxylic anhydride and unsaturated vinyl monomers other than unsaturated vinyl monomers containing carboxylic anhydride as structural units, epoxy compounds, polyurethane resins, acrylic homopolymers, copolymers of acrylic acid and other copolymerizable monomers, and salts of these with primary amines, secondary amines, and tertiary amines, etc. These sizing agents may be used alone or in combination of two or more.
[0279] Among them, from the viewpoint of the mechanical strength of the obtained polyamide composition, as the sizing agent, it is preferred to use at least one selected from the group consisting of a copolymer containing an unsaturated vinyl monomer containing carboxylic anhydride and an unsaturated vinyl monomer other than the unsaturated vinyl monomer containing carboxylic anhydride as a structural unit, an epoxy compound, and a polyurethane resin. In addition, it is more preferred to use at least one selected from the group consisting of a copolymer containing an unsaturated vinyl monomer containing carboxylic anhydride and an unsaturated vinyl monomer other than the unsaturated vinyl monomer containing carboxylic anhydride as a structural unit, and a polyurethane resin.
[0280] The glass fiber or carbon fiber is obtained by applying the above-mentioned sizing agent to the fibers using a known method such as a roll coater in a known production process of the fibers to produce a fiber bundle, and drying the fiber bundle to cause continuous reaction.
[0281] The fiber bundle may be used directly in the form of a roving, or may be used in the form of chopped glass strands after further undergoing a cutting step.
[0282] The sizing agent is preferably applied (added) in an amount of about 0.2 mass % to about 3 mass % inclusive, and more preferably about 0.3 mass % to about 2 mass % inclusive, based on the total mass of the glass fiber or carbon fiber in terms of solid fraction.
[0283] When the amount of the sizing agent added is equal to or greater than the above lower limit in terms of solid fraction relative to the total mass of the glass fibers or carbon fibers, the fibers can be more effectively bundled. On the other hand, when the amount of the sizing agent added is equal to or less than the above upper limit in terms of solid fraction relative to the total mass of the glass fibers or carbon fibers, the thermal stability of the obtained polyamide composition can be further improved.
[0284] The fiber bundle may be dried after the cutting step, or the fiber bundle may be cut after being dried.
[0285] As inorganic fillers other than glass fiber and carbon fiber, from the viewpoint of improving the strength, rigidity and surface appearance of the molded product, preferably wollastonite, kaolin, mica, talc, calcium carbonate, magnesium carbonate, potassium titanate fiber, aluminum borate fiber or clay. More preferably wollastonite, kaolin, mica, talc, calcium carbonate or clay. Further preferably wollastonite, kaolin, mica or talc. Particularly preferably wollastonite, mica or talc. These inorganic fillers can be used alone or in combination of two or more.
[0286] From the viewpoint of improving toughness and the surface appearance of molded products, the average particle size of inorganic fillers other than glass fibers and carbon fibers is preferably 0.01 μm to 38 μm, more preferably 0.03 μm to 30 μm, further preferably 0.05 μm to 25 μm, further preferably 0.10 μm to 20 μm, and particularly preferably 0.15 μm to 15 μm.
[0287] When the average particle diameter of the inorganic filler other than glass fiber and carbon fiber is below the upper limit, a polyamide composition having better toughness and surface appearance of a molded product can be obtained. On the other hand, when the average particle diameter is above the lower limit, a polyamide composition having better balance in cost and powder handling and physical properties (fluidity, etc.) can be obtained.
[0288] For needle-shaped inorganic fillers such as wollastonite other than glass fiber and carbon fiber, the number average particle size (hereinafter sometimes referred to as "average particle size") is taken as the average particle size. In addition, when the cross section is not circular, the maximum value of its length is taken as the (number average) particle size.
[0289] The number average particle length of the needle-shaped inorganic filler (hereinafter sometimes simply referred to as “average particle length”) is preferably within a numerical range calculated from the preferred range of the above-mentioned number average particle size and the preferred range of the aspect ratio (l / d) of the number average particle length (l) to the number average particle size (d) described below.
[0290] The aspect ratio (l / d) of the number average particle length (l) of the inorganic filler having a needle-like shape to the number average particle diameter (d) is preferably 1.5 or more and 10 or less, more preferably 2.0 or more and 5 or less, and further preferably 2.5 or more and 4 or less, from the viewpoint of improving the surface appearance of the molded product and preventing wear of metal parts of an injection molding machine or the like.
[0291] Inorganic fillers other than glass fiber and carbon fiber may be surface-treated using a silane coupling agent, a titanate coupling agent, or the like.
[0292] Examples of the silane coupling agent include the same silane coupling agents as exemplified above with respect to the glass fiber and the carbon fiber.
[0293] Among them, aminosilanes are preferred as the silane coupling agent.
[0294] Such a surface treatment agent may be used to treat the surface of the inorganic filler in advance, or may be added when the polyamide and the inorganic filler are mixed. In addition, the amount of the surface treatment agent added is preferably 0.05% by mass or more and 1.5% by mass or less relative to the total mass of the inorganic filler.
[0295] [(D) Content of inorganic filler]
[0296] The content of the inorganic filler relative to the total mass of the polyamide composition is preferably 10 mass % to 60 mass %, more preferably 10 mass % to 55 mass %, further preferably 10 mass % to 50 mass %, further preferably 15 mass % to 50 mass %, further preferably 15 mass % to 45 mass %, particularly preferably 15 mass % to 40 mass %, further particularly preferably 20 mass % to 40 mass %, and most preferably 20 mass % to 35 mass %.
[0297] When the content of the inorganic filler is greater than the above lower limit, the strength and rigidity of the obtained polyamide composition are further improved. On the other hand, when the content of the inorganic filler is less than the above upper limit, a polyamide composition with better extrudability and moldability can be obtained.
[0298] 《(E) Other ingredients》
[0299] The polyamide composition of the present embodiment may further contain, in addition to the above-mentioned components (A) to (D), one or more other components (E) selected from the group consisting of a lubricant, a heat stabilizer, a flame retardant other than a phosphorus-containing flame retardant, a nucleating agent, other polymers, and other additives.
[0300] [Lubricant]
[0301] The lubricant is not particularly limited, and examples thereof include higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, higher fatty acid amides, etc. The lubricant can also be used as a molding improver.
[0302] (Higher fatty acids)
[0303] Examples of the higher fatty acid include linear or branched saturated or unsaturated aliphatic monocarboxylic acids having 8 to 40 carbon atoms.
[0304] Examples of the linear saturated aliphatic monocarboxylic acid having 8 to 40 carbon atoms include lauric acid, palmitic acid, stearic acid, behenic acid, and montanic acid.
[0305] Examples of the branched saturated aliphatic monocarboxylic acid having 8 to 40 carbon atoms include isopalmitic acid and isostearic acid.
[0306] Examples of the linear unsaturated aliphatic monocarboxylic acid having 8 to 40 carbon atoms include oleic acid and erucic acid.
[0307] Examples of the branched unsaturated aliphatic monocarboxylic acid having 8 to 40 carbon atoms include vaccenic acid and the like.
[0308] Among them, as the higher fatty acid, stearic acid or montanic acid is preferred.
[0309] (Higher fatty acid metal salt)
[0310] The higher fatty acid metal salt refers to a metal salt of a higher fatty acid.
[0311] Examples of the metal element of the metal salt include Group 1 elements, Group 2 elements, and Group 3 elements of the periodic table, zinc, and aluminum.
[0312] Examples of the Group 1 elements of the periodic table include sodium and potassium.
[0313] Examples of the Group 2 elements of the periodic table include calcium and magnesium.
[0314] Examples of the Group 3 elements of the periodic table include scandium and yttrium.
[0315] Among them, elements of Group 1 and Group 2 of the periodic table or aluminum are preferred, and sodium, potassium, calcium, magnesium or aluminum is more preferred.
[0316] Specific examples of the higher fatty acid metal salt include calcium stearate, aluminum stearate, zinc stearate, magnesium stearate, calcium montanate, sodium montanate, and calcium palmitate.
[0317] Among them, as the higher fatty acid metal salt, a metal salt of montanic acid or a metal salt of stearic acid is preferred.
[0318] (Higher fatty acid esters)
[0319] Higher fatty acid esters refer to esters of higher fatty acids and alcohols.
[0320] As the higher fatty acid ester, an ester of an aliphatic carboxylic acid having 8 to 40 carbon atoms and an aliphatic alcohol having 8 to 40 carbon atoms is preferred.
[0321] Examples of the aliphatic alcohol having 8 to 40 carbon atoms include stearyl alcohol, behenyl alcohol, and lauryl alcohol.
[0322] Specific examples of the higher fatty acid ester include stearyl stearate and behenyl behenate.
[0323] (Higher fatty acid amide)
[0324] Higher fatty acid amide refers to an amide compound of higher fatty acid.
[0325] Examples of the higher fatty acid amides include stearamide, oleamide, erucamide, ethylenebisstearamide, ethylenebisoleamide, N-stearyl stearamide, and N-stearyl erucamide.
[0326] These higher fatty acids, higher fatty acid metal salts, higher fatty acid esters, and higher fatty acid amides may be used alone or in combination of two or more.
[0327] The content of the lubricant in the polyamide composition is preferably 0.01% by mass or more and 1% by mass or less, and more preferably 0.1% by mass or more and 1% by mass or less, relative to the total mass of the polyamide composition.
[0328] When the content of the lubricant is at least the above lower limit, the moldability of the polyamide composition can be further improved, while when the content of the lubricant is at most the above upper limit, the rigidity of the molded article can be further improved.
[0329] [Heat stabilizer]
[0330] Examples of the heat stabilizer include phenolic heat stabilizers, phosphorus-containing heat stabilizers, amine heat stabilizers, metal salts of elements of Group 3, Group 4, and Groups 11 to 14 of the periodic table, and halides of alkali metals and alkaline earth metals, but are not limited thereto.
[0331] (Phenolic heat stabilizer)
[0332] Examples of the phenolic heat stabilizer include, but are not limited to, hindered phenol compounds. Hindered phenol compounds have the property of imparting excellent heat resistance and light resistance to resins such as polyamide or fibers.
[0333] Examples of the hindered phenol compound include N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid amide), triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 3,9-bis{2-[ 3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 1,3,5-tri(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, etc., but are not limited thereto.
[0334] These hindered phenol compounds may be used alone or in combination of two or more.
[0335] In particular, from the viewpoint of improving heat aging resistance, N,N′-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] is preferred as the hindered phenol compound.
[0336] When a phenolic heat stabilizer is used, the content of the phenolic heat stabilizer in the polyamide composition is preferably 0.01 mass % to 1 mass %, and more preferably 0.1 mass % to 1 mass %, based on the total mass of the polyamide composition.
[0337] When the content of the phenolic heat stabilizer is within the above range, the heat aging resistance of the polyamide composition can be further improved, and the amount of gas generated can be further reduced.
[0338] (Phosphorus-containing heat stabilizer)
[0339] Examples of the phosphorus-containing heat stabilizer include pentaerythritol-type phosphite compounds, trioctyl phosphite, trilauryl phosphite, tridecyl phosphite, diphenyl octyl phosphite, triisodecyl phosphite, diisodecyl phenyl phosphite, ditridecyl phenyl phosphite, isooctyl diphenyl phosphite, isodecyl diphenyl phosphite, tridecyl diphenyl phosphite, triphenyl phosphite, tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(2,4-di-tert-butyl-5-methylphenyl) phosphite, tris(butoxyethyl) phosphite Phosphite, 4,4'-butylidene bis(3-methyl-6-tert-butylphenyl) ester-tetradecyl ester, diphosphite, 4,4'-isopropylidene diphenyl ester-tetra(C12-C15 mixed alkyl) ester, phosphite, 4,4'-isopropylidene bis(2-tert-butylphenyl) ester-di(nonylphenyl) ester, tris(biphenyl) phosphite, 1,1,3-tris(2-methyl-5-tert-butyl-4-hydroxyphenyl) butane diphosphite tetra(tridecyl) ester, diphosphite, 4,4'-butylidene bis(3-methyl-6-tert-butylphenyl) ester-tetra(tridecyl) ester, diphosphite, 4,4'-isopropylidene diphenyl ester-tetra(C12-C15 mixed alkyl) ester, diphosphite, 4,4'-isopropylidene bis(2-tert-butylphenyl) ester-di(nonylphenyl) ester, tris(biphenyl) phosphite, 1,1,3-tris(2-methyl-5-tert-butyl-4-hydroxyphenyl) butane diphosphite tetra(tridecyl) ester, Propyl diphenyl ester-tetra(C1-C15 mixed alkyl) ester, tris(mixed monononylphenyl, dinonylphenyl) phosphite, 4,4'-isopropylidene bis(2-tert-butylphenyl) phosphite-di(nonylphenyl) ester, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(3,5-di-tert-butyl-4-hydroxyphenyl) phosphite, hydrogenated 4,4'-isopropylidene diphenyl polyphosphite, bis[4,4'-butylidene bis(3-methyl-6-tert-butylphenyl)]-1,6-hexanediol diphosphite di(octylphenyl) ester, 1,1,3-tris(2-methyl-4- Hydroxy-5-tert-butylphenyl) butane triphosphite hexa(tridecyl) ester, tris(4,4'-isopropylidenebis(2-tert-butylphenyl)) phosphite, tris(1,3-distearoyloxyisopropyl) phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphite-octyl ester, 2,2'-methylenebis(3-methyl-4,6-di-tert-butylphenyl) phosphite-2-ethylhexyl ester, 4,4'-biphenylene diphosphite tetra(2,4-di-tert-butyl-5-methylphenyl) ester and 4,4'-biphenylene diphosphite tetra(2,4-di-tert-butylphenyl) ester, etc., but are not limited thereto.
[0340] These phosphorus-containing heat stabilizers may be used alone or in combination of two or more.
[0341] Among them, the phosphorus-containing heat stabilizer is preferably at least one selected from the group consisting of pentaerythritol-type phosphite compounds and tris(2,4-di-tert-butylphenyl) phosphite from the viewpoint of further improving the heat aging resistance of the polyamide composition and reducing the amount of gas generated.
[0342] Examples of the pentaerythritol type phosphite compound include pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-phenyl ester, pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-methyl ester, pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-2-ethylhexyl ester, pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-isodecyl ester, pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-lauryl ... Phosphate 2,6-di-tert-butyl-4-methylphenyl ester-isotridecyl ester, Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-stearyl ester, Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-cyclohexyl ester, Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-benzyl ester, Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-ethyl cellosolve ester, Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-butyl carbitol ester 、Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-octylphenyl ester、Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-nonylphenyl ester、Pentaerythritol diphosphite bis(2,6-di-tert-butyl-4-methylphenyl) ester、Pentaerythritol diphosphite bis(2,6-di-tert-butyl-4-ethylphenyl) ester、Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-2,6-di-tert-butylphenyl ester、Pentaerythritol diphosphite 2,6-di-tert-butyl-4-methyl Phenyl ester-2,4-di-tert-butylphenyl ester, pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-2,4-di-tert-octylphenyl ester, pentaerythritol diphosphite 2,6-di-tert-butyl-4-methylphenyl ester-2-cyclohexylphenyl ester, pentaerythritol diphosphite 2,6-di-tert-pentyl-4-methylphenyl ester-phenyl ester, pentaerythritol diphosphite di(2,6-di-tert-pentyl-4-methylphenyl) ester and pentaerythritol diphosphite di(2,6-di-tert-octyl-4-methylphenyl) ester, etc., but are not limited thereto.
[0343] These pentaerythritol-type phosphite compounds may be used alone or in combination of two or more.
[0344] Among them, as the pentaerythritol phosphite compound, from the viewpoint of reducing the amount of gas generated by the polyamide composition, preferably at least one selected from the group consisting of pentaerythritol diphosphite di(2,6-di-tert-butyl-4-methylphenyl) ester, pentaerythritol diphosphite di(2,6-di-tert-butyl-4-ethylphenyl) ester, pentaerythritol diphosphite di(2,6-di-tert-amyl-4-methylphenyl) ester and pentaerythritol diphosphite di(2,6-di-tert-octyl-4-methylphenyl) ester, and more preferably pentaerythritol diphosphite di(2,6-di-tert-butyl-4-methylphenyl) ester.
[0345] When a phosphorus-containing heat stabilizer is used, the content of the phosphorus-containing heat stabilizer in the polyamide composition is preferably 0.01 mass % to 1 mass %, more preferably 0.1 mass % to 1 mass %, based on the total mass of the polyamide composition.
[0346] When the content of the phosphorus-containing heat stabilizer is within the above range, the heat aging resistance of the polyamide composition can be further improved, and the amount of gas generated can be further reduced.
[0347] (Amine heat stabilizer)
[0348] Examples of the amine heat stabilizer include 4-acetoxy-2,2,6,6-tetramethylpiperidine, 4-stearoyloxy-2,2,6,6-tetramethylpiperidine, 4-acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(phenylacetoxy)-2,2,6,6-tetramethylpiperidine, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-methoxy-2,2,6,6-tetramethylpiperidine, 4-stearoyloxy-2,2,6,6-tetramethylpiperidine, 4-cyclohexyloxy-2,2,6,6-tetramethylpiperidine, and 4-benzyloxy-2,2,6,6-tetramethylpiperidine. 4-(phenylcarbamoyloxy)-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidinyl) carbonate, bis(2,2,6,6-tetramethyl-4-piperidinyl) oxalate, bis(2,2,6,6-tetramethyl-4-piperidinyl) malonate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, Bis(2,2,6,6-tetramethyl-4-piperidinyl) terephthalate, 1,2-bis(2,2,6,6-tetramethyl-4-piperidinyl) ethane, α,α'-bis(2,2,6,6-tetramethyl-4-piperidinyl) p-xylene, bis(2,2,6,6-tetramethyl-4-piperidinyl) toluene-2,4-dicarbamate, bis(2,2,6,6-tetramethyl-4-piperidinyl) hexamethylene-1,6-dicarbamate, tris(2,2,6,6-tetramethyl-4 Benzene-1,3,4-tricarboxylic acid tris(2,2,6,6-tetramethyl-4-piperidinyl) ester, 1-[2-{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy}butyl]-4-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]-2,2,6,6-tetramethylpiperidine, 1,2,3,4-butanetetracarboxylic acid, 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxaspiro(5.5)undecane]diethanol condensate, etc., but are not limited thereto.
[0349] These amine heat stabilizers may be used alone or in combination of two or more.
[0350] When an amine heat stabilizer is used, the content of the amine heat stabilizer in the polyamide composition is preferably 0.01 mass % to 1 mass %, more preferably 0.1 mass % to 1 mass %, based on the total mass of the polyamide composition.
[0351] When the content of the amine heat stabilizer is within the above range, the heat aging resistance of the polyamide composition can be further improved, and the amount of gas generated can be further reduced.
[0352] Among them, the copper salt is preferably one or more selected from the group consisting of cuprous iodide, cuprous bromide, cupric bromide, cuprous chloride and cupric acetate, and more preferably one or more selected from the group consisting of cuprous iodide and cupric acetate. When the preferred copper salts listed above are used, a polyamide composition having better heat aging resistance and capable of more effectively suppressing metal corrosion of the screw and barrel during extrusion (hereinafter, sometimes referred to as "metal corrosion") can be obtained.
[0353] When a copper salt is used as a heat stabilizer, the content of the copper salt in the polyamide composition is preferably 0.01 mass % to 0.60 mass % and more preferably 0.02 mass % to 0.40 mass % relative to the total mass of the polyamide ((A-1) crystalline polyamide and (A-2) amorphous polyamide).
[0354] When the content of the copper salt is within the above range, the heat aging resistance of the polyamide composition can be further improved, and copper precipitation and metal corrosion can be more effectively suppressed.
[0355] In addition, from the viewpoint of improving the heat aging resistance of the polyamide composition, 6 The content concentration of the copper element derived from the copper salt per one million parts by mass of the polyamide ((A-1) crystalline polyamide and (A-2) amorphous polyamide) is preferably 10 parts by mass or more and 2000 parts by mass or less, more preferably 30 parts by mass or more and 1500 parts by mass or less, and even more preferably 50 parts by mass or more and 500 parts by mass or less.
[0356] (Alkali and alkaline earth metal halides)
[0357] Examples of the halides of alkali metals and alkaline earth metals include potassium iodide, potassium bromide, potassium chloride, sodium iodide, sodium chloride, and the like, but are not limited thereto.
[0358] These alkali metal and alkaline earth metal halides may be used alone or in combination of two or more.
[0359] Among them, as the halide of alkali metal and alkaline earth metal, from the viewpoint of improving heat aging resistance and suppressing metal corrosion, at least one selected from the group consisting of potassium iodide and potassium bromide is preferred, and potassium iodide is more preferred.
[0360] When using halides of alkali metals and alkaline earth metals, the content of halides of alkali metals and alkaline earth metals in the polyamide composition is preferably from 0.05 parts by mass to 20 parts by mass, and more preferably from 0.2 parts by mass to 10 parts by mass, relative to 100 parts by mass of the polyamide ((A-1) crystalline polyamide and (A-2) amorphous polyamide).
[0361] When the content of the halide of an alkali metal or an alkaline earth metal is within the above range, the heat aging resistance of the polyamide composition can be further improved, and copper precipitation and metal corrosion can be more effectively suppressed.
[0362] The heat stabilizer components described above may be used alone or in combination of two or more.
[0363] Among them, hindered phenol compounds are preferred as the heat stabilizer from the viewpoint of further improving the heat aging resistance of the polyamide composition.
[0364] [Nucleating agent]
[0365] The nucleating agent refers to a substance that can obtain at least any one of the following effects (1) to (3) by adding.
[0366] (1) The effect of increasing the crystallization peak temperature of the polyamide composition.
[0367] (2) The effect of reducing the difference between the extrapolated starting temperature and the extrapolated ending temperature of the crystallization peak.
[0368] (3) The effect of making the spherulites of the obtained molded product finer or more uniform in size.
[0369] Examples of the nucleating agent include talc, boron nitride, mica, kaolin, silicon nitride, potassium titanate, and molybdenum disulfide, but the nucleating agent is not limited thereto.
[0370] The nucleating agents may be used alone or in combination of two or more.
[0371] Among them, as the nucleating agent, talc or boron nitride is preferred from the viewpoint of the nucleating agent effect.
[0372] In addition, the number average particle size of the nucleating agent is preferably 0.01 μm or more and 10 μm or less because the effect of the nucleating agent is high.
[0373] The number average particle size of the nucleating agent can be measured using the following method. First, the molded product is dissolved in a solvent such as formic acid that can dissolve polyamide. Then, 100 or more nucleating agents are arbitrarily selected from the obtained insoluble components. Then, the particles are observed using an optical microscope or a scanning electron microscope, and the particle size is measured, thereby the number average particle size of the nucleating agent can be obtained.
[0374] The content of the nucleating agent in the polyamide composition of the present embodiment is preferably 0.001% by mass to 1% by mass, more preferably 0.001% by mass to 0.5% by mass, and even more preferably 0.001% by mass to 0.09% by mass, relative to the total mass of the polyamide composition.
[0375] When the content of the nucleating agent is at least the above lower limit, the heat resistance of the polyamide composition tends to be further improved, while when the content of the nucleating agent is at most the above upper limit, a polyamide composition having further excellent toughness can be obtained.
[0376] [Other polymers]
[0377] As other polymers, there are no particular restrictions as long as they are polymers other than polyamide, and examples thereof include polyester, liquid crystal polyester, polyphenylene sulfide, polyphenylene ether, polycarbonate, polyarylate, phenol resin, epoxy resin, etc. As polyesters, examples thereof include polybutylene terephthalate, polytrimethylene terephthalate, polyethylene terephthalate, polyethylene naphthalate, etc., but are not limited thereto.
[0378] The content of other polymers is preferably 1% by mass or more and 30% by mass or less, more preferably 5% by mass or more and 20% by mass or less, and further preferably 5% by mass or more and 15% by mass or less relative to the total amount of polyamide in the polyamide composition. When the content of other polymers is within the above range, a polyamide composition having better heat resistance and mold release properties can be prepared.
[0379] [Other additives]
[0380] The polyamide composition obtained by the production method of the present embodiment may contain other additives commonly used in polyamide compositions in addition to the above-mentioned components within a range that does not impair the effects of the polyamide composition obtained by the production method of the present embodiment. Examples of other additives include colorants such as pigments and dyes (including color masterbatches), flame retardants, fibrillating agents, fluorescent bleaching agents, plasticizers, antioxidants, ultraviolet absorbers, antistatic agents, flow improvers, and extenders.
[0381] When the polyamide composition obtained by the production method of this embodiment contains other additives, the content of other additives varies depending on the type of other additives, the use of the polyamide composition, etc., and therefore is not particularly limited as long as it is within a range that does not impair the effects of the polyamide composition obtained by the production method of this embodiment.
[0382] [Flame retardant additives]
[0383] Anhydrous zinc borate can be used as a flame retardant aid. When anhydrous zinc borate is selected, the ratio of anhydrous zinc borate to (B) phosphorus-containing flame retardant is preferably 1:98 to 20:80 from the viewpoint of flame retardancy efficiency, and more preferably 3:97 to 10:90.
[0384] <Method for producing polyamide composition>
[0385] The method for producing the polyamide composition of the present embodiment is not particularly limited as long as it includes a step of melt-kneading the raw material components including the above-mentioned (A) polyamide, (B) phosphorus-containing flame retardant, (C) polyamide elastomer, and (D) inorganic filler. For example, it is preferably a method including a step of melt-kneading the raw material components including the above-mentioned (A) polyamide, (B) phosphorus-containing flame retardant, (C) polyamide elastomer, and (D) inorganic filler using an extruder, and setting the set temperature of the extruder to be less than the melting peak temperature Tm+30°C of the above-mentioned polyamide composition.
[0386] Examples of methods for melt-kneading the raw material components including polyamide include: a method in which (A) polyamide, (C) polyamide elastomer and other raw materials are mixed using a tumbler, a Henschel mixer or the like, and the mixture is supplied to a melt kneader for kneading; a method in which other raw materials including (B) a phosphorus-containing flame retardant and (D) an inorganic filler are blended into the molten (A) polyamide and (C) polyamide elastomer using a side feeder in a single-screw or twin-screw extruder; and the like.
[0387] Regarding the method of supplying the components constituting the polyamide composition to the melt-kneading machine, all the components may be supplied at once to the same supply port, or the components may be supplied from different supply ports.
[0388] The melt kneading temperature is preferably about 250° C. or higher and about 350° C. or lower in terms of resin temperature.
[0389] The melt-kneading time is preferably about 0.25 minutes or more and about 5 minutes or less.
[0390] The apparatus for performing melt kneading is not particularly limited, and for example, a known melt kneading machine such as a single-screw or twin-screw extruder, a Banbury mixer, or a mixing roll can be used.
[0391] The melt kneader is preferably a co-rotating twin-screw extruder having a screw diameter of 30 mm or more, and the ratio (L / D) of the barrel length (L) to the length (D) of the screw diameter of the twin-screw extruder is preferably 35 or more. When the L / D of the extruder is within the above range, appropriate kneading can be applied during kneading without large heat generation, and the crystal domain diameter of the amorphous polyamide can be adjusted to the preferred range of the present application.
[0392] The screw speed (N) of the twin-screw extruder is preferably 350 rpm or more, and the ratio Q / N of the screw speed (N) to the discharge amount (Q) is preferably 1.14 or less. When Q / N is within the above range, appropriate kneading can be applied during kneading without large heat generation, and the crystal domain diameter of the amorphous polyamide can be adjusted to the preferred range of the present application.
[0393] Furthermore, when adding (B) a phosphorus-containing flame retardant and (D) an inorganic filler, in order to improve the kneading efficiency of the (B) phosphorus-containing flame retardant and (D) an inorganic filler, it is preferred that the (A) polyamide and (C) polyamide elastomer are supplied from the upstream supply port of the twin-screw extruder after dry blending, and the (B) phosphorus-containing flame retardant and (D) an inorganic filler are supplied from the downstream first supply port of the twin-screw extruder.
[0394] <Molding>
[0395] The molded article of the present embodiment is obtained by molding the above-mentioned polyamide composition.
[0396] The molded article of the present embodiment is excellent in low-temperature impact resistance, load deflection temperature, electrical properties, and flame retardancy by using the above-mentioned polyamide composition.
[0397] The molded product of this embodiment can be obtained by molding the above-mentioned polyamide composition using a known molding method such as press molding, injection molding, gas-assisted injection molding, welding molding, extrusion molding, blow molding, film molding, hollow molding, multilayer molding, melt spinning, etc.
[0398] "use"
[0399] The polyamide composition of the present embodiment can be used particularly for applications where heat resistance, flame retardancy, and electrical properties are important, and can be suitably used for electric / electronic components and automotive electric / electronic components.
[0400] The above-mentioned electrical components can be used as power adapters for office equipment, measuring instruments, chassis, internal parts of electrical equipment, home appliance-related equipment, etc., as industrial equipment, recording media or their drivers, sensor devices, terminal blocks, secondary batteries, fuel cells or solar cells in the energy / environmental field, electrical and electronic components used in solar power generation, geothermal power generation, wind power generation, smart meters, etc., electrical components constituting power transmission equipment, cable terminals, automotive parts, in particular, connection structures for solar power generation modules such as module connectors for solar power generation and junction boxes for solar cells, and parts for hybrid vehicles / electric vehicles.
[0401] Example
[0402] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to the following examples.
[0403] The present invention is described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples. First, the measurement methods, evaluation methods, and raw materials used in the examples and comparative examples are shown below. It should be noted that in this example, 1 kg / cm 2 Indicates 0.098MPa.
[0404] <Composition>
[0405] [(A) Polyamide]
[0406] A-1a: Polyamide 66 (synthesized by the method described below)
[0407] A-1b: Polyamide 12
[0408] A-2: Polyamide 6I (synthesized by the synthesis method described below)
[0409] [(B) Phosphorus-containing flame retardants]
[0410] B1: Phosphinic acid flame retardant, aluminum diethylphosphinate (manufactured by Clariant, trade name "Exolit OP1230")
[0411] B2: Phosphinic acid flame retardant, composite salt of aluminum diethylphosphinate and aluminum ethylphosphonate (manufactured by Weihai Run Company, trade name "MADP8900BS")
[0412] [Other flame retardants]
[0413] B3: Melamine cyanurate (manufactured by Nissan Chemical Co., Ltd., trade name "MC4500")
[0414] B4: Anhydrous zinc borate (produced by Kinsei Matec, Firebrake 500)
[0415] [(C) Polyamide elastomer]
[0416] C1: PA6 elastomer, manufactured by Sanyo Chemical Co., Ltd., trade name "PELESTAT NC6321"
[0417] C2: PA12 elastomer, manufactured by Arkema, trade name "PEBAX MV2080"
[0418] C3: Other elastomers, maleic anhydride modified hydrogenated styrene-butadiene copolymers
[0419] (Made by Asahi Kasei, trade name "TUFTEC M1943")
[0420] C4: Other elastomers, maleic anhydride modified ethylene-octene copolymers
[0421] (Manufactured by DuPont, trade name "FUSABOND N493")
[0422] [(D) Inorganic filler]
[0423] D-1: Glass fiber (GF) (manufactured by Nippon Electric Glass Co., Ltd., trade name "ECS03T275H", average fiber diameter 10 μmφ, cut length 3 mm)
[0424] <Manufacturing of polyamide>
[0425] The following is a detailed description of each method for producing crystalline polyamide A-1 and amorphous polyamide A-2. It should be noted that the crystalline polyamide A-1 and amorphous polyamide A-2 obtained by the following production method were dried in a nitrogen gas stream to adjust the water content to about 0.2% by mass, and then used as raw materials for the polyamide compositions in the examples and comparative examples described below.
[0426] [Synthesis example 1]
[0427] (Synthesis of Crystalline Polyamide A-1 (Polyamide 66))
[0428] The polymerization reaction of polyamide was carried out by the "hot melt polymerization method" as follows.
[0429] First, 1500g of an equimolar salt of adipic acid and hexamethylenediamine was dissolved in 1500g of distilled water to prepare an equimolar 50% by mass uniform aqueous solution of the raw monomers. The aqueous solution was put into an autoclave with an internal volume of 5.4L and replaced with nitrogen. Then, water vapor was slowly extracted while stirring at a temperature of about 110°C or more and about 150°C or less to concentrate the solution to a concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. This state was maintained for 1 hour until the internal temperature reached 245°C, and the reaction was continued for 1 hour while slowly extracting water vapor and maintaining the pressure at 1.8MPa. Then, the pressure was reduced for 1 hour. Next, the autoclave was maintained under a reduced pressure of 650 Torr (86.66kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C. Next, the strands were formed from the lower spinneret (nozzle) by nitrogen pressure, water-cooled, cut, and discharged in pellet form. The pellets were then dried at 100°C in a nitrogen atmosphere for 12 hours to obtain crystalline polyamide A-1 (polyamide 66).
[0430] The obtained crystalline polyamide A-1 (polyamide 66) had Mw(A)=40,000, Mw / Mn=2.0, and a melting point Tm of 260°C.
[0431] [Synthesis example 2]
[0432] (Synthesis of amorphous polyamide A-2 (polyamide 6I))
[0433] The polymerization reaction of polyamide was carried out by the "hot melt polymerization method" as follows.
[0434] First, 1500g of an equimolar salt of isophthalic acid and hexamethylenediamine, 1.5 mol% excess of adipic acid relative to all equimolar salt components, and 0.5 mol% of acetic acid relative to all equimolar salt components were dissolved in 1500g of distilled water to prepare an equimolar 50% uniform aqueous solution of the raw monomers. Then, water vapor was slowly extracted while stirring at a temperature of about 110°C or more and about 150°C or less to concentrate the solution to a concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. This state was maintained for 1 hour until the internal temperature reached 245°C, and the reaction was continued for 1 hour while slowly extracting water vapor and maintaining the pressure at 1.8MPa. Then, the pressure was reduced over 30 minutes. Next, the autoclave was maintained under a reduced pressure of 650 Torr (86.66kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C. Next, the strands were formed from the lower spinneret (nozzle) by nitrogen pressure, water-cooled, cut, and discharged in pellet form. The pellets were then dried at 100° C. in a nitrogen atmosphere for 12 hours to obtain amorphous polyamide A-2 (polyamide 6I).
[0435] The content of the isophthalic acid unit in the dicarboxylic acid unit of the obtained amorphous polyamide A-2 (polyamide 6I) was 100 mol %, Mw(B)=20000, and Mw / Mn=2.0.
[0436] <Measurement Methods of Physical Properties>
[0437] The following various physical properties were measured using the raw material polyamide and the polyamide composition after adjusting the water content.
[0438] [Physical properties 1]
[0439] (Molecular weight and molecular weight distribution of polyamide composition)
[0440] Mw (weight average molecular weight) and Mn (number average molecular weight) were measured using a gel permeation chromatograph (GPC) (HLC-8020 manufactured by Tosoh Corporation) and a hexafluoroisopropanol solvent, and were converted to a PMMA (polymethyl methacrylate) standard sample (manufactured by Polymer Laboratories). The molecular weight distribution Mw / Mn was calculated from these values.
[0441] (Melting peak temperature Tm (melting point))
[0442] The measurement was performed using Diamond-DSC manufactured by PERKIN-ELMER Co., Ltd. in accordance with JIS-K7121. Specifically, the measurement was performed as follows.
[0443] First, in a nitrogen atmosphere, about 10 mg of a sample is heated from room temperature to 300°C to 350°C at a heating rate of 20°C / min according to the melting point of the sample. The maximum peak temperature of the endothermic peak (melting peak) that appears at this time is defined as Tm (°C).
[0444] It should be noted that the details of the raw materials are as follows.
[0445] (Polyamide)
[0446] Crystalline polyamide A-1a (polyamide 66): The polyamide obtained by the above synthesis was used.
[0447] Crystalline polyamide A-1b (polyamide 12): (Rilsamid AMN P20TL manufactured by Arkema)
[0448] Amorphous polyamide A-2 (polyamide 6I): The polyamide obtained by the above synthesis was used.
[0449] (Phosphorus flame retardant)
[0450] B-1 Phosphinic acid flame retardant, aluminum diethylphosphinate (manufactured by Clariant, trade name "Exolit OP1230" powder)
[0451] B-2 Phosphinic acid flame retardant, composite salt of aluminum diethylphosphinate and aluminum ethylphosphonate (manufactured by Weihai Wairun Company, trade name "MADP8900 BS")
[0452] (Polyamide elastomer)
[0453] PA6 elastomer, manufactured by Sanyo Chemical Co., Ltd., trade name "PELESTAT NC6321"
[0454] PA12 elastomer, manufactured by Arkema, trade name "PEBAX MV2080"
[0455] (Inorganic filling materials)
[0456] Inorganic filler: Inorganic filler E-1 (glass fiber (GF) (manufactured by Nippon Electric Glass Co., Ltd., trade name "ECS03T275H", average fiber diameter 10 μmφ, cut length 3 mm))
[0457] [Evaluation 1]
[0458] (Charpy impact strength at 23°C)
[0459] For each polyamide composition pellet, an injection molding machine [PS40E: manufactured by Nissei Plastic Industry Co., Ltd.] was used, and the injection + holding time was set to 25 seconds, the cooling time was 15 seconds, the mold temperature was 80°C, and the molten resin temperature was 270°C to mold a molded piece of ISO 3167, multi-purpose test piece type A. Then, the molded piece of multi-purpose test piece type A was processed into a notched test piece according to ISO2818. For the obtained notched test piece, the Charpy impact strength was measured at 23°C in accordance with JIS K7111 (ISO179). The larger the value of the Charpy impact strength, the better the mechanical strength is evaluated.
[0460] [Evaluation 2]
[0461] (Charpy impact strength at -40℃)
[0462] For each polyamide composition pellet, an injection molding machine [PS40E: manufactured by Nissei Plastic Industry Co., Ltd.] was used, and the injection + holding time was set to 25 seconds, the cooling time was 15 seconds, the mold temperature was 80°C, and the molten resin temperature was 270°C to mold a molded piece of ISO 3167, multi-purpose test piece type A. Then, the molded piece of multi-purpose test piece type A was processed into a notched test piece according to ISO2818. For the obtained notched test piece, the Charpy impact strength was measured at -40°C according to JIS K7111 (ISO179). The larger the value of the Charpy impact strength, the better the impact strength is evaluated.
[0463] [Evaluation 3]
[0464] (23℃ dart impact test)
[0465] The pellets of each polyamide composition were injection molded using an injection molding machine [PS40E: manufactured by Nissei Plastic Industry Co., Ltd.], with the injection + holding time set to 25 seconds, the cooling time to 15 seconds, the mold temperature to 80°C, and the molten resin temperature to 270°C. The injection molded test pieces (70 mm in length × 70 mm in width, 3 mm in thickness) were measured under an environment of 23°C using a dart impact tester "CEAST9340" manufactured by Instron. The test piece was sandwiched between cylinders with a diameter of 50 mm and fixed, and an impactor weighing 6.55 kg was dropped vertically from a height of 500 mm to the center of the flat plate, and its impact energy J was measured. The larger the value of the impact energy J, the better the impact strength was evaluated to be.
[0466] [Evaluation 4]
[0467] (-40℃ dart impact test)
[0468] The injection molded test piece (70 mm in length × 70 mm in width, 3 mm in thickness) was placed in a thermostatic chamber at -40°C for 5 hours and then measured using a dart impact tester "CEAST9340" manufactured by Instron. The test piece was clamped between cylinders with a diameter of 50 mm and fixed, and an impactor weighing 6.55 kg was dropped vertically from a height of 500 mm to the center of the plate, and its impact energy J was measured. The larger the value of the impact energy J, the better the impact strength was evaluated to be.
[0469] [Evaluation 5]
[0470] (Deflection Temperature Under Load (DTUL))
[0471] The pellets of each polyamide composition were molded into 80 mm × 10 mm × 4 mm pieces using an injection molding machine [PS40E: manufactured by Nissei Plastic Industry Co., Ltd.], with the injection + holding time set to 25 seconds, cooling time 15 seconds, mold temperature 80°C, and molten resin temperature 270°C. The heat deformation temperature was measured under a load of 1.82 MPa according to JIS K 7191-2: 2015. The higher the load deflection temperature, the better the heat resistance was evaluated.
[0472] [Evaluation 6]
[0473] (Flame retardancy)
[0474] The measurement was carried out using the method of UL94 (a standard established by Under Writers Laboratories Inc. in the United States). It should be noted that the test pieces (length 127 mm, width 12.7 mm, thickness 0.75 mm and length 127 mm, width 12.7 mm, thickness 1.50 mm) were made by installing the mold of the UL test piece in an injection molding machine (PS40E manufactured by Nissei Plastic Industry Co., Ltd.) (mold temperature = 100°C) and molding each polyamide composition at a barrel temperature of 290°C. Regarding the injection pressure, it was carried out at a pressure of +2% of the full filling pressure during the molding of the UL test piece. Regarding the flame retardant grade, the UL94 standard (vertical burning test) was used to evaluate which grade it was equivalent to among V-0, V-1, and V-2. In addition, the smaller the numerical value of the grade, the higher the flame retardancy.
[0475] <Production of Polyamide Composition>
[0476] [Example 1 to Example 10 and Comparative Example 1 to Comparative Example 7]
[0477] A polyamide composition was produced as follows using (A) polyamide, (B) phosphorus-containing flame retardant, (C) polyamide elastomer, and (D) inorganic filler in the types and ratios described in the following tables.
[0478] The raw material polyamide (A) was dried in a nitrogen gas stream to adjust the water content to about 0.2% by mass and then used as a raw material for the polyamide composition.
[0479] As a production apparatus for the polyamide composition, a twin-screw extruder (manufactured by Toshiba Machine Co., Ltd., trade name “TEM-58SX” (L / D=53.8)) was used.
[0480] In the twin-screw extruder, the temperature from the upstream supply port to the die was set to the melting point Tm2+20°C of each (A) crystalline polyamide produced in the above production example, the screw speed was 350 rpm, and the discharge rate was 400 kg / hour (Q / N=1.14).
[0481] (A) polyamide and (C) polyamide elastomer were dry-blended to give the types and ratios shown in the following tables, and then supplied from the upstream supply port of a twin-screw extruder, (B) phosphorus-containing flame retardant was supplied from the first supply port on the downstream side of the twin-screw extruder, and (D) glass fiber was supplied from the second supply port on the downstream side, and the molten kneaded product extruded from the die was cooled in the form of strands and granulated to obtain pellets of a polyamide composition. The pellets of the polyamide composition thus obtained were dried in a nitrogen gas stream to adjust the water content in the polyamide composition to 500 ppm or less.
[0482] [Table 1]
[0483]
[0484] As can be seen from Table 1, the polyamide composition containing the specified amounts of (A) polyamide, (B) phosphorus-containing flame retardant, (C) polyamide elastomer, and (D) inorganic filler maintains UL94 V-0 flame retardancy, is excellent in low-temperature impact resistance and load deflection temperature, and is also excellent in electrical properties.
[0485] Industrial Applicability
[0486] The polyamide composition of the present embodiment has the above-mentioned properties and can be suitably used in particular for electric / electronic parts and automotive electric / electronic parts.
[0487] According to the polyamide composition of the present embodiment, it is possible to provide a polyamide composition having excellent low-temperature impact resistance, electrical properties, load deflection temperature, and flame retardancy.
Claims
1. A polyamide composition, wherein The polyamide composition comprises: 20 wt % to 60 wt % of (A) polyamide, 10 wt % to 30 wt % of (B) phosphorus-containing flame retardant, 2 wt % to 20 wt % of (C) polyamide elastomer, and 10 wt % to 60 wt % of (D) inorganic filler.
2. The polyamide composition according to claim 1, wherein The phosphorus-containing flame retardant (B) comprises at least one phosphinate selected from the group consisting of a phosphinate represented by the following general formula (1), a diphosphinate represented by the following general formula (2) and their condensates, and a complex salt of a phosphinate and a phosphonate represented by the following general formula (3). In the general formula (1), R 11 and R 12 Each independently represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; M n11+ is a metal ion with a valence of n11; M is an element belonging to Group 2 or Group 15 of the periodic table, a transition element, zinc or aluminum; n11 is 2 or 3; when n11 is 2 or 3, the presence of multiple R 11 and multiple R 12 Each can be the same or different; In general formula (2), R 21 and R 22 Each independently represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; Y 21 is an alkylene group having 1 to 10 carbon atoms or an arylene group having 6 to 10 carbon atoms; M' x m21+ is a metal ion with a valence of m21; M' is an element belonging to Group 2 or Group 15 of the periodic table, a transition element, zinc or aluminum; n21 is an integer of 1 to 3; when n21 is 2 or 3, the presence of multiple R 21 , multiple R 22 and multiple Y 21 Each may be the same or different; m21 is 2 or 3; x is 1 or 2; when x is 2, the multiple M's present may be the same or different; n21, x and m21 are integers satisfying the relationship 2×n21=m21×x; In the general formula (3), R1, R2 and R3 are each independently an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; M m+ is a metal ion; M is an element belonging to Group 2 or Group 15 of the periodic table, a transition element, zinc or aluminum; m is 2 or 3; when m is 2 or 3, the multiple R1s, multiple R2s and multiple R3s present may be the same or different; a and b are both greater than 0.01 and less than 10, satisfying m=a+2b.
3. The polyamide composition according to claim 1 or 2, wherein (B) The phosphorus-containing flame retardant comprises a phosphinic acid metal salt or a phosphinic acid-phosphonic acid composite metal salt.
4. The polyamide composition according to claim 1 or 2, wherein (C) The polyamide elastomer is a polyamide elastomer based on polyamide 6.
5. The polyamide composition according to claim 1 or 2, wherein The (A) polyamide is (A-1) a crystalline polyamide.
6. The polyamide composition according to claim 1 or 2, wherein The (A) polyamide further includes (A-2) amorphous polyamide.
7. The polyamide composition according to claim 6, wherein The (A-2) amorphous polyamide contains 50 mol % or more of isophthalic acid units in all the dicarboxylic acid units constituting the amorphous polyamide.
8. The polyamide composition according to claim 6, wherein The (A-2) amorphous polyamide contains 75 mol % or more of isophthalic acid units in all the dicarboxylic acid units constituting the amorphous polyamide.
9. The polyamide composition according to claim 6, wherein The (A-2) amorphous polyamide contains 100 mol % of isophthalic acid units in all the dicarboxylic acid units constituting the amorphous polyamide.
Citation Information
Patent Citations
Polycarbonate resin composition
JP1996073729A
Method for producing dialkylphosphinate
JP2005179362A
Flame-retardant polyamide 12 molding composition for railroad use
JP2017043762A
Polyamide composition, method for producing the same, and molded article
JP2021050323A
Improved copolyetherester
WO2021257531A1